Inorganic solid electrolyte-containing composition, sheet for all-solid-state secondary battery, and all-solid-state secondary battery, and method for manufacturing sheet for all-solid-state secondary battery and all-solid-state secondary battery

CN114930594BActive Publication Date: 2026-10-27FUJIFILM CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202180008047.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-25
Filing Date
2021-01-07
Publication Date
2026-10-27
Estimated Expiration
2041-01-07

AI Technical Summary

Benefits of technology

[0074]本发明能够提供一种能够制作分散稳定性及处理性的分散特性优异,并且能够通过抑制固体粒子之间的界面电阻的上升来实现低电阻的构成层的构成层的含无机固体电解质组合物。并且,本发明能够提供一种具有由该含无机固体电解质组合物构成的层的全固态二次电池用片材及全固态二次电池。此外,本发明能够提供一种使用该含无机固体电解质组合物的全固态二次电池用片材及全固态二次电池的制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114930594B_ABST
    Figure CN114930594B_ABST
Patent Text Reader

Abstract

Provided is an inorganic solid electrolyte-containing composition having excellent dispersion stability and handling properties, and capable of achieving a low-resistance constitution layer by suppressing an increase in interfacial resistance between solid particles, a sheet for a full solid-state secondary battery using the inorganic solid electrolyte-containing composition, a full solid-state secondary battery, and a method for manufacturing a sheet for a full solid-state secondary battery and a full solid-state secondary battery. The inorganic solid electrolyte-containing composition is an inorganic solid electrolyte-containing composition for a full solid-state secondary battery containing an inorganic solid electrolyte, a polymer binder, a metal element-containing compound, and a dispersion medium, the metal element-containing compound is a compound capable of supplying a metal element constituting a molecule as an ion to a polymer forming the polymer binder, the polymer binder is dissolved in the dispersion medium, and the metal element-containing compound exists in a solid state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composition containing an inorganic solid electrolyte, a sheet for an all-solid-state secondary battery, an all-solid-state secondary battery, and a method for manufacturing the sheet for an all-solid-state secondary battery and the all-solid-state secondary battery. Background Technology

[0002] A secondary battery is a rechargeable battery that has a negative electrode, a positive electrode, and an electrolyte sandwiched between the negative and positive electrodes, and can be charged and discharged by causing specific metal ions such as lithium ions to move back and forth between the two electrodes.

[0003] Non-aqueous electrolyte secondary batteries using organic electrolytes are widely used as such secondary batteries. However, to further improve battery performance, various electrolyte compositions used in the manufacture of non-aqueous electrolyte secondary batteries are being researched. For example, Patent Document 1 discloses a composition for an energy storage device containing anti-blocking agents such as fatty acid amides, fatty acid esters, and fatty acid metal salts, adhesive particles, and an aqueous medium, wherein the ratio of the content of adhesive particles to the content of the aforementioned anti-blocking agent is greater than 1 and less than 4000. Furthermore, Patent Document 2 discloses an electrolyte composition containing an organic solvent and a lithium carboxylate-boron trifluoride complex obtained by reacting lithium carboxylate with boron trifluoride and / or a boron trifluoride complex, which serves as the electrolyte for lithium-ion secondary batteries.

[0004] However, non-aqueous electrolyte secondary batteries using organic electrolytes are prone to liquid leakage and are susceptible to internal short circuits due to overcharging or over-discharging, thus requiring further improvements in safety and reliability.

[0005] In this context, all-solid-state secondary batteries using inorganic solid electrolytes instead of organic electrolytes have attracted attention. The negative electrode, electrolyte, and positive electrode of this all-solid-state secondary battery are all made of solids, which can significantly improve the safety and reliability of batteries using organic electrolytes and also extend their lifespan. Furthermore, all-solid-state secondary batteries can be configured with electrodes and electrolytes directly arranged and connected in series. Therefore, compared to secondary batteries using non-aqueous electrolytes with organic electrolytes, they can achieve higher energy density and are expected to be used in electric vehicles or large-scale storage batteries.

[0006] In this type of all-solid-state secondary battery, the constituent layers (solid electrolyte layer, negative electrode active material layer, positive electrode active material layer, etc.) are formed using a composition containing electrolyte, active material, etc. For example, Patent Document 2 also describes a composition for a solid electrolyte containing an organic solvent, a lithium carboxylate-boron trifluoride complex as the electrolyte, and a matrix polymer.

[0007] However, in recent years, inorganic solid electrolytes, especially oxide-based and sulfide-based inorganic solid electrolytes, have attracted much attention as materials forming the constituent layer, exhibiting high ionic conductivity close to that of organic electrolytes. However, as materials forming the constituent layer of an all-solid-state secondary battery, materials (compositions) containing the aforementioned inorganic solid electrolytes have not been studied in Patent Documents 1 and 2.

[0008] Previous technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Application Publication No. 2015-005526

[0011] Patent Document 2: Japanese Patent Application Publication No. 2013-209355 Summary of the Invention

[0012] The technical problem to be solved by the invention

[0013] Because the constituent layers of an all-solid-state secondary battery are formed from solid particles (inorganic solid electrolyte, active material, conductive additives, etc.), the interfacial contact between these particles is essentially limited. Therefore, compared to non-aqueous electrolyte secondary batteries, all-solid-state secondary batteries are more prone to increased interfacial resistance (reduced ionic conductivity), leading to a decrease in their cycle performance. In particular, when polymer binders are present in the constituent layers, the interfacial resistance between solid particles tends to increase further.

[0014] Furthermore, when the constituent layer of an all-solid-state secondary battery is formed from solid particles, from the viewpoint of improving the battery performance (ionic conductivity, cycle characteristics, etc.) of the all-solid-state secondary battery with the constituent layer formed therefrom, it is required that the material forming the constituent layer has the characteristics of maintaining the excellent dispersibility of the freshly prepared solid particles (dispersion stability) and having the characteristics of having appropriate viscosity and excellent flowability (processability).

[0015] However, in recent years, the research and development of high-performance and practical electric vehicles has progressed rapidly, placing increasingly higher demands on the battery performance of all-solid-state rechargeable batteries. To meet these demands, it is necessary to develop constituent layer forming materials that combine high levels of dispersion stability and processability while being able to form low-resistivity constituent layers.

[0016] The objective of this invention is to provide an inorganic solid electrolyte composition with excellent dispersion stability and processability, and an inorganic solid electrolyte composition that can achieve a low-resistance constituent layer by suppressing the increase of interfacial resistance between solid particles. Furthermore, the objective of this invention is to provide a sheet for an all-solid-state secondary battery using the inorganic solid electrolyte composition, an all-solid-state secondary battery, and a method for manufacturing the sheet for an all-solid-state secondary battery and an all-solid-state secondary battery.

[0017] means for solving technical problems

[0018] The inventors have conducted various studies on the constituent materials of inorganic solid electrolytes and the constituent layers formed therefrom. They discovered that by coexisting a metal-containing compound that can provide metal ions to the polymer binder with the inorganic solid electrolyte particles, and by specifying the dispersion state (solubility) of the polymer binder and the metal-containing compound relative to the dispersion medium, it is possible to suppress re-aggregation or precipitation caused by the inorganic solid electrolyte particles over time, and to suppress excessive viscosity increases (tackification). Furthermore, it was discovered that this inorganic solid electrolyte composition, for example, through coating and heating, can suppress the increase in interfacial resistance between particles while simultaneously bonding the inorganic solid electrolytes together to form a film. As a result, it was discovered that by using this inorganic solid electrolyte composition as a constituent layer forming material, it is possible to realize a sheet for all-solid-state secondary batteries with a low-resistance constituent layer, as well as an all-solid-state secondary battery with low resistance and excellent cycle characteristics. Based on these insights, the present invention was completed through further repeated research.

[0019] That is, the above-mentioned problems are solved through the following solutions.

[0020] <1> An inorganic solid electrolyte composition for use in an all-solid-state secondary battery, comprising an inorganic solid electrolyte having conductive ions of metals belonging to Group 1 or Group 2 of the periodic table, a polymer binder, a metal-containing compound, and a dispersion medium, wherein,

[0021] Metal-containing compounds are compounds that can donate metal elements, which constitute molecules, as ions into polymers that form polymer adhesives.

[0022] The polymer binder is dissolved in the dispersion medium, and the metal-containing compound exists in a solid state.

[0023] <2> According to the inorganic solid electrolyte composition described in <1>, wherein,

[0024] Compounds containing metallic elements are dispersed in a dispersion medium.

[0025] <3> The inorganic solid electrolyte composition according to <1> or <2>, wherein,

[0026] The average particle size of compounds containing metallic elements is 0.1–5 μm.

[0027] <4> The inorganic solid electrolyte composition according to any one of <1> to <3>, wherein,

[0028] Compounds containing metallic elements are organometallic salts.

[0029] <5> The inorganic solid electrolyte composition according to any one of <1> to <4>, wherein,

[0030] Anions of compounds containing metallic elements that have the negative common logarithm [pKa] of the acid dissociation constant of their conjugate acids, ranging from -2 to 20.

[0031] <6> The inorganic solid electrolyte composition according to any one of <1> to <5>, wherein,

[0032] Metal-containing compounds have anions derived from organic compounds containing 6 to 21 carbon atoms.

[0033] <7> The inorganic solid electrolyte composition according to any one of <1> to <6>, wherein,

[0034] The metallic elements that make up compounds containing metallic elements include those belonging to Group 1 or Group 2 of the periodic table.

[0035] <8> The inorganic solid electrolyte composition according to any one of <1> to <7>, wherein,

[0036] The metallic elements that make up compounds containing metallic elements include lithium.

[0037] <9> The inorganic solid electrolyte composition according to any one of <1> to <8>, wherein,

[0038] The polymer that forms the polymeric adhesive has a polymeric chain in its main chain having at least one bond selected from urethane bonds, urea bonds, amide bonds, imide bonds and ester bonds or carbon-carbon double bonds.

[0039] <10> The inorganic solid electrolyte composition according to any one of <1> to <9>, wherein,

[0040] The polymer forming the polymer adhesive comprises a constituent having functional groups selected from the functional group (A) below.

[0041] <Functional Groups (A)>

[0042] Hydroxyl, amino, carboxyl, sulfonyl, phosphate, phosphonic acid, thioalkyl, heterocyclic, carboxylic anhydride

[0043] <11> The inorganic solid electrolyte composition according to <10>, wherein,

[0044] The pKa of the conjugate acid of the anion in the derivative metal-containing compound is greater than the pKa of the functional group.

[0045] <12> The inorganic solid electrolyte composition according to <1> or <11>, wherein,

[0046] The difference between the pKa of the conjugate acid of the anion and the pKa of the functional group in the derived metal-containing compound is greater than 2 [(pKa of the conjugate acid) - (pKa of the functional group)].

[0047] <13> The inorganic solid electrolyte composition according to any one of <1> to <12>, wherein,

[0048] When the inorganic solid electrolyte composition is heated to above 80°C, the solubility of the polymer binder in the dispersion medium after heating becomes less than that of the polymer binder before heating in the same dispersion medium.

[0049] <14> The inorganic solid electrolyte composition according to any one of <1> to <13>, wherein,

[0050] When the inorganic solid electrolyte composition is concentrated to a total concentration of 30% by mass or more of the polymer binder and the metal element compound in the inorganic solid electrolyte composition, the solubility of the concentrated polymer binder in the dispersion medium becomes less than the solubility of the polymer binder in the dispersion medium before concentration.

[0051] <15> The inorganic solid electrolyte composition according to any one of <1> to <14>, wherein,

[0052] When a film is formed from an inorganic solid electrolyte composition, the solubility of the polymer binder present in the layer in the dispersion medium previously contained in the inorganic solid electrolyte composition becomes less than the solubility of the polymer binder previously contained in the inorganic solid electrolyte composition in the aforementioned dispersion medium.

[0053] <16> An inorganic solid electrolyte composition according to any one of <1> to <15>, wherein the composition contains an active substance.

[0054] <17> The inorganic solid electrolyte composition according to any one of <1> to <16> contains a conductive aid.

[0055] <18> The inorganic solid electrolyte composition according to any one of <1> to <17>, wherein,

[0056] Inorganic solid electrolytes are sulfide-based inorganic solid electrolytes.

[0057] <19> The inorganic solid electrolyte composition according to any one of <1> to <18>, wherein,

[0058] The viscosity at a temperature of 23℃ and a shear rate of 10 / s is 300–4000 cP.

[0059] <20> A sheet for an all-solid-state secondary battery, having a layer composed of an inorganic solid electrolyte composition as described in any one of <1> to <19> above.

[0060] <21> The sheet for all-solid-state secondary batteries as described in <20>, wherein,

[0061] The polymer binder exists in the layer as particles with an average particle size of 10–800 nm.

[0062] <22> The sheet for all-solid-state secondary batteries according to <20> or <21>, wherein,

[0063] The solubility of the polymer binder present in the above-mentioned layer in the dispersion medium previously contained in the inorganic solid electrolyte composition becomes less than the solubility of the polymer binder previously contained in the inorganic solid electrolyte composition in the aforementioned dispersion medium.

[0064] <23> An all-solid-state secondary battery, which sequentially comprises a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein,

[0065] At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is composed of a sheet for all-solid-state secondary batteries as described in any one of <20> to <22>.

[0066] <24> A method for manufacturing a sheet for an all-solid-state secondary battery, wherein the inorganic solid electrolyte composition described in any one of <1> to <19> is used to form a film.

[0067] <25> The method for manufacturing sheet for all-solid-state secondary batteries according to <24>, wherein,

[0068] While the polymer binder contained in the inorganic solid electrolyte composition is cured into particles, a film is formed.

[0069] <26> The method for manufacturing sheets for all-solid-state secondary batteries according to <24> or <25>, wherein,

[0070] While reducing the solubility of the polymer binder contained in the inorganic solid electrolyte composition in the dispersion medium, a film is formed on the inorganic solid electrolyte composition.

[0071] <27> A method for manufacturing a sheet for an all-solid-state secondary battery according to any one of <24> to <26>, wherein a film is formed by heating a composition containing an inorganic solid electrolyte to 80°C or higher.

[0072] <28> A method for manufacturing an all-solid-state secondary battery, wherein the all-solid-state secondary battery is manufactured by any one of the manufacturing methods described in <24> to <27> above.

[0073] Invention Effects

[0074] This invention provides an inorganic solid electrolyte composition that produces a constituent layer with excellent dispersion characteristics, including dispersion stability and processability, and achieves low resistance by suppressing the rise of interfacial resistance between solid particles. Furthermore, this invention provides a sheet for an all-solid-state secondary battery having a layer composed of this inorganic solid electrolyte composition, and an all-solid-state secondary battery. Additionally, this invention provides a method for manufacturing the sheet for an all-solid-state secondary battery using the inorganic solid electrolyte composition and an all-solid-state secondary battery. Attached Figure Description

[0075] Figure 1 This is a longitudinal sectional view illustrating a preferred embodiment of the all-solid-state secondary battery of the present invention. Detailed Implementation

[0076] In this invention, the numerical range represented by “~” refers to the range encompassed by the values ​​recorded before and after “~” as the lower limit and upper limit values.

[0077] In this invention, the designation of a compound (e.g., when referred to as a compound by appending a compound at the end) means that in addition to the compound itself, it also includes its salt and its ions. Furthermore, it refers to derivatives that include modifications to the introduced substituents or other components without impairing the effects of this invention.

[0078] In this invention, (meth)acrylic acid refers to one or both of acrylic acid and methacrylic acid. The same applies to (meth)acrylates.

[0079] In this invention, the term "substituent, linking group, etc." (hereinafter referred to as "substituent, etc.") that is not explicitly stated as substituted or unsubstituted means that the group may also have suitable substituents. Therefore, in this invention, even when simply described as a YYY group, the YYY group includes not only those without substituents but also those with substituents. This also applies to compounds where substitution or unsubstituent is not explicitly stated. As a preferred substituent, substituent Z, described later, can be cited as an example.

[0080] In this invention, when multiple substituents, etc., are represented by specific symbols, or when multiple substituents, etc., are specified simultaneously or selectively, it means that each substituent, etc., may be the same as or different from each other. Furthermore, even without special explanation, when multiple substituents, etc., are adjacent, it means that they may be linked together or fused together to form a ring.

[0081] In this invention, polymer refers to polymer, but has the same meaning as the so-called high molecular weight compound.

[0082] [Inorganic solid electrolyte composition]

[0083] The inorganic solid electrolyte composition of the present invention contains an inorganic solid electrolyte having conductivity of ions of metals belonging to Group 1 or Group 2 of the periodic table, a polymer binder, a metal-containing compound, and a dispersion medium.

[0084] In this composition containing inorganic solid electrolytes, the polymer binder is dissolved in the dispersion medium and may or may not be adsorbed onto the inorganic solid electrolytes. The polymer binder functions as a binder that bonds solid particles, such as inorganic solid electrolytes (and coexisting active substances, conductive additives), to each other (e.g., inorganic solid electrolytes to each other, inorganic solid electrolytes and active substances, active substances to each other) within at least a layer formed from the inorganic solid electrolyte composition. Furthermore, it also functions as a binder for bonding current collectors and solid particles. In the inorganic solid electrolyte composition, the polymer binder may or may not have the function of bonding solid particles to each other.

[0085] On the other hand, in inorganic solid electrolyte compositions, the metal element compounds exist in a solid state and are preferably dispersed in a dispersion medium.

[0086] The inorganic solid electrolyte composition of the present invention is preferably a slurry formed by dispersing an inorganic solid electrolyte and a metal element compound in a dispersion medium. In this case, the polymer binder preferably has the function of dispersing solid particles in the dispersion medium.

[0087] In this invention, by coexisting a metal-containing compound that is insoluble in the dispersion medium with a polymer binder (solubilizing binder) that is soluble in the dispersion medium, the composition can achieve dispersion stability and processability (dispersion characteristics) that are equal to or greater than those of a solubilizing binder. At the same time, for the first time, the composition layer achieves low resistance that is equal to or greater than that of a polymer binder (particulate binder) that is insoluble in the dispersion medium.

[0088] By using the inorganic solid electrolyte composition of the present invention, which has excellent dispersion properties, as the constituent layer forming material, it is possible to realize a constituent layer with low resistance, having a flat surface and excellent surface properties, and a sheet for an all-solid-state secondary battery having the constituent layer, as well as an all-solid-state secondary battery with low resistance and excellent cycle characteristics.

[0089] Furthermore, in the manner in which the active material layer formed on the current collector is formed by the inorganic solid electrolyte composition of the present invention, a strong and tight bond between the current collector and the active material layer can be achieved, and the cycle characteristics can be further improved without causing an increase in resistance.

[0090] The exact reasons are unclear, but it is believed that the polymer binder, which is in a dissolved state in the inorganic solid electrolyte composition, can interact with the metal-containing compound and solidify into particles when forming the constituent layer.

[0091] That is, it is believed that in the inorganic solid electrolyte composition, the polymer binder is dissolved in the dispersion medium. Therefore, even if the metal element compound exists in a solid state, compared with the case where the polymer binder exists in particulate form, the re-aggregation or precipitation of inorganic solid electrolyte particles entrained in the polymer binder can be effectively suppressed not only immediately after the preparation of the inorganic solid electrolyte composition, but also after a period of time. As a result, the high dispersibility immediately after preparation can be stably maintained (excellent dispersion stability), and excessive increase in viscosity can be suppressed, exhibiting good flowability (excellent processability).

[0092] It is believed that if the inorganic solid electrolyte composition of the present invention, which exhibits excellent dispersion stability and processability, is used to form the constituent layer, the formation of re-agglomerates or precipitates of inorganic solid electrolyte particles can be suppressed even during the film formation of the constituent layer (e.g., during coating and drying). This suppresses deviations in the contact state between inorganic solid electrolyte particles in the constituent layer. In particular, when the inorganic solid electrolyte composition contains active substances, specific particles such as active substances are less likely to be unevenly distributed in the constituent layer (solid particles are uniformly disposed in the constituent layer). As a result, the increase in interfacial resistance between solid particles and the resistance of the constituent layer can be suppressed. Furthermore, during film formation, especially during coating, the inorganic solid electrolyte composition flows appropriately (smoothly), without surface roughness due to insufficient or excessive flow, and without surface roughness caused by blockage at the discharge point during film formation (excellent surface properties of the coated surface), resulting in a constituent layer with good surface properties. Thus, a constituent layer with a flat surface and low resistance (high conductivity) can be produced.

[0093] On the other hand, when metal-containing compounds are used in the film formation of inorganic solid electrolyte compositions, they interact with the polymer binder, reducing the solubility of the polymer binder in the dispersion medium and causing the dissolved polymer binder to solidify or precipitate into particles. Since the solidified polymer binder partially (adsorbs) rather than completely coats the surface of the inorganic solid electrolyte particles, the contact between the inorganic solid electrolyte particles is not hindered by the presence of the polymer binder. Furthermore, the contact between the inorganic solid electrolyte particles effectively constructs ion conduction pathways (suppressing the increase in interfacial resistance between the inorganic solid electrolyte particles) while simultaneously binding the inorganic solid electrolyte particles.

[0094] All-solid-state secondary batteries with this low-resistance constituent layer exhibit high conductivity (ionic conductivity and electronic conductivity). Furthermore, due to the low resistance of all-solid-state secondary batteries, energy loss is minimal under high current conditions, enabling high-speed charge-discharge at high currents in addition to normal charging and discharging. Moreover, because overcurrent is less likely to occur during charging and discharging, battery characteristics are maintained not only under normal charging and discharging conditions but also under repeated high-speed charge-discharge cycles, exhibiting excellent cycle performance.

[0095] When the active material layer is formed from the inorganic solid electrolyte composition of the present invention, as described above, the constituent layer is formed while maintaining a highly (uniform) dispersion state immediately after preparation. Therefore, it is believed that the contact (adhesion) between the polymer binder and the current collector surface is not hindered by the preferentially precipitated solid particles, and the polymer binder can contact (adhere to) the current collector surface while dispersed with the solid particles. Thus, the electrode sheet for all-solid-state secondary batteries, in which the active material layer of the inorganic solid electrolyte composition of the present invention is formed on the current collector, can achieve a strong adhesion between the current collector and the active material. Furthermore, the all-solid-state secondary battery in which the active material layer of the inorganic solid electrolyte composition of the present invention is formed on the current collector exhibits a strong adhesion between the current collector and the active material and further improves cycle characteristics; in addition to excellent cycle characteristics, it also achieves improved conductivity.

[0096] The inorganic solid electrolyte composition of the present invention can be preferably used as a forming material (constituent layer forming material) for sheets (including electrode sheets for all-solid-state secondary batteries) or solid electrolyte layers or active material layers of all-solid-state secondary batteries. In particular, it can be preferably used as a forming material for negative electrode sheets or negative electrode active material layers of all-solid-state secondary batteries containing negative electrode active materials that expand and contract significantly due to charging and discharging, in which high cycle characteristics and high conductivity can also be achieved.

[0097] The inorganic solid electrolyte composition of the present invention further comprises, in addition to containing an inorganic solid electrolyte, an active substance and a conductive additive, etc. (the composition of this manner is referred to as an electrode composition.)

[0098] The following describes the components contained in the inorganic solid electrolyte composition of the present invention and the components that may be contained therein.

[0099] <Inorganic Solid Electrolytes>

[0100] The inorganic solid electrolyte composition of the present invention contains an inorganic solid electrolyte.

[0101] In this invention, inorganic solid electrolyte refers to an inorganic solid electrolyte, which is a solid electrolyte capable of allowing ions to move within it. It is clearly distinguished from organic solid electrolytes (such as polymeric electrolytes represented by polyethylene oxide (PEO) and organic electrolyte salts represented by lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)) from the perspective of not containing organic materials as the primary ion-conducting material. Furthermore, since inorganic solid electrolytes are solid in their stable state, they generally do not dissociate or ionize into cations and anions. In this respect, they are clearly distinguished from inorganic electrolyte salts (such as LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), and LiCl) that dissociate or ionize into cations and anions in electrolytes or polymers. There are no particular limitations as long as the inorganic solid electrolyte possesses the ion conductivity of metals belonging to Group 1 or Group 2 of the periodic table; it generally does not possess electronic conductivity. In the case of the all-solid-state secondary battery of the present invention being a lithium-ion battery, it is preferable that the inorganic solid electrolyte has the ionic conductivity of lithium ions.

[0102] The aforementioned inorganic solid electrolyte can be appropriately selected from solid electrolyte materials commonly used in all-solid-state secondary batteries. For example, as inorganic solid electrolytes, (i) sulfide-based inorganic solid electrolytes, (ii) oxide-based inorganic solid electrolytes, (iii) halide-based inorganic solid electrolytes, and (iv) hydride-based solid electrolytes can be mentioned. From the viewpoint of forming a better interface between the active material and the inorganic solid electrolyte, sulfide-based inorganic solid electrolytes are preferred.

[0103] (i) Sulfide-based inorganic solid electrolytes

[0104] Preferably, the sulfide-based inorganic solid electrolyte contains sulfur atoms and has ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table, and is an electronically insulating compound. Preferably, the sulfide-based inorganic solid electrolyte contains at least Li, S, and P as elements and has lithium-ion conductivity, but may also contain other elements besides Li, S, and P depending on the purpose or circumstances.

[0105] As a sulfide-based inorganic solid electrolyte, for example, a lithium-ion conductive inorganic solid electrolyte that satisfies the composition represented by the following formula (S1) can be cited.

[0106] L a1 M b1 P c1 S d1 A e1 (S1)

[0107] In the formula, L represents an element selected from Li, Na, and K, preferably Li. M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge. A represents an element selected from I, Br, Cl, and F. a1 to e1 represent the composition ratio of each element, where a1:b1:c1:d1:e1 satisfies 1–12:0–5:1:2–12:0–10. a1 is preferably 1–9, more preferably 1.5–7.5. b1 is preferably 0–3, more preferably 0–1. d1 is preferably 2.5–10, more preferably 3.0–8.5. e1 is preferably 0–5, more preferably 0–3.

[0108] As described below, the composition ratio of each element can be controlled by adjusting the amount of raw material compounds used in the manufacture of sulfide-based inorganic solid electrolytes.

[0109] Sulfide-based inorganic solid electrolytes can be amorphous (glass), crystallized (glass-ceramic), or partially crystallized. For example, Li-PS-based glasses or Li-PS-based glass-ceramics containing Li, P, and S can be used.

[0110] Sulfide-based inorganic solid electrolytes can be manufactured by reacting at least two of the following raw materials: lithium sulfide (Li2S), phosphorus sulfide (e.g., phosphorus pentasulfide (P2S5)), monomeric phosphorus, monomeric sulfur, sodium sulfide, hydrogen sulfide, lithium halides (e.g., LiI, LiBr, LiCl), and sulfides of the element represented by M above (e.g., SiS2, SnS, GeS2).

[0111] In Li-PS glass and Li-PS glass-ceramics, the ratio of Li₂S to P₂S₅, in terms of the molar ratio of Li₂S:P₂S₅, is preferably 60:40 to 90:10, more preferably 68:32 to 78:22. Setting the Li₂S to P₂S₅ ratio within this range improves lithium-ion conductivity. Specifically, the lithium-ion conductivity is preferably set to 1 × 10⁻⁶. -4 S / cm or higher, more preferably 1×10 -3 S / cm or higher. Although no specific upper limit is set, it is actually 1×10⁻⁶. -1 Below S / cm.

[0112] As specific examples of sulfide-based inorganic solid electrolytes, combinations of raw materials are illustrated below. For example, Li₂S-P₂S₅, Li₂S-P₂S₅-LiCl, Li₂S-P₂S₅-H₂S, Li₂S-P₂S₅-H₂S-LiCl, Li₂S-LiI-P₂S₅, Li₂S-LiI-Li₂O-P₂S₅, Li₂S-LiBr-P₂S₅, Li₂S-Li₂O-P₂S₅, Li₂S-Li₃PO₄-P₂S₅, Li₂S-P₂S₅-P₂O₅, Li₂S-P₂S₅-SiS₂, Li₂S-P₂S₅-SiS₂-LiCl, Li₂S-P₂S₅-SnS, and Li₂S-P₂S₅-Al₂ can be cited. S3, Li2S-GeS2, Li2S-GeS2-ZnS, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, Li2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li 10 GeP2S 12 And so on. The mixing ratio of each raw material is not limited. As a method for synthesizing sulfide-based inorganic solid electrolyte materials using this raw material composition, for example, an amorphization method can be mentioned. As an amorphization method, examples include mechanical polishing, solution processing, and melt quenching. Processing at room temperature is possible, thereby simplifying the manufacturing process.

[0113] (ii) Oxide-based inorganic solid electrolytes

[0114] Oxide-based inorganic solid electrolytes are preferably compounds containing oxygen atoms, possessing ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation properties.

[0115] For oxide-based inorganic solid electrolytes, the preferred ionic conductivity is 1×10⁻⁶. -6 S / cm or higher, preferably 5×10 -6 S / cm or higher, especially preferably 1×10 -5 S / cm or higher. Although no specific upper limit is set, it is actually 1×10⁻⁶. -1 Below S / cm.

[0116] As a specific example of a compound, Li can be cited. xa La yaTiO3 [xa satisfies 0.3≤xa≤0.7, ya satisfies 0.3≤ya≤0.7.] (LLT); Li xb La yb Zr zb M bb mb O nb (M bb It consists of one or more elements selected from Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn. xb satisfies 5 ≤ ​​xb ≤ 10, yb satisfies 1 ≤ yb ≤ 4, zb satisfies 1 ≤ zb ≤ 4, mb satisfies 0 ≤ mb ≤ 2, and nb satisfies 5 ≤ ​​nb ≤ 20. Li xc B yc M cc zc O nc (M cc It is an element selected from C, S, Al, Si, Ga, Ge, In, and Sn. xc satisfies 0 < xc ≤ 5, yc satisfies 0 < yc ≤ 1, zc satisfies 0 < zc ≤ 1, and nc satisfies 0 < nc ≤ 6. ); Li xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd (xd satisfies 1≤xd≤3, yd satisfies 0≤yd≤1, zd satisfies 0≤zd≤2, ad satisfies 0≤ad≤1, md satisfies 1≤md≤7, nd satisfies 3≤nd≤13.) ; Li (3-2xe) M ee xe D ee O(xe) represents a number greater than 0 and less than 0.1, M ee This represents a divalent metal atom. (D) ee Represents a halogen atom or a combination of two or more halogen atoms; Li xf Si yf O zf (xf satisfies 1 ≤ xf ≤ 5, yf satisfies 0 < yf ≤ 3, zf satisfies 1 ≤ zf ≤ 10.) ; Li xg S yg O zg (xg satisfies 1≤xg≤3, yg satisfies 0<yg≤2, zg satisfies 1≤zg≤10.) ; Li3BO3; Li3BO3-Li2SO4; Li2O-B2O3-P2O5; Li2O-SiO2; Li6BaLa2Ta2O 12 Li3PO (4-3 / 2w) N w(w satisfies w < 1); Li has a LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zn 0.25 GeO4; La with a perovskite-type crystal structure 0.55 Li 0.35 TiO3; LiTi2P3O with a NASICON (Natrium super ionic conductor) crystal structure 12 Li 1+xh+yh (Al, Ga) xh (Ti, Ge) 2-xh Si yh P 3-yh O 12 (xh satisfies 0≤xh≤1, yh satisfies 0≤yh≤1); Li7La3Zr2O has a garnet-type crystal structure. 12 (LLZ) etc.

[0117] Furthermore, phosphorus compounds containing Li, P, and O are preferred. Examples include lithium phosphate (Li3PO4); LiPON, in which a nitrogen atom replaces part of the oxygen atom in lithium phosphate; and LiPOD. 1 (D 1 Preferably, it contains one or more elements selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, and Au.

[0118] Furthermore, LiA can be preferably used. 1 ON(A 1 It consists of one or more elements selected from Si, B, Ge, Al, C, and Ga.

[0119] (iii) Halogen-based inorganic solid electrolytes

[0120] The preferred inorganic solid electrolytes are compounds containing halogen atoms, possessing conductivity of ions belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation properties.

[0121] There are no particular limitations on the type of inorganic solid electrolyte, such as LiCl, LiBr, LiI, and compounds like Li3YBr6 and Li3YCl6 described in ADVANCED MATERIALS, 2018, 30, 1803075. Among these, Li3YBr6 and Li3YCl6 are preferred.

[0122] (iv) Hydride-based inorganic solid electrolytes

[0123] Hydride-based inorganic solid electrolytes are preferably compounds containing hydrogen atoms, possessing ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation properties.

[0124] There are no particular limitations as hydride-based inorganic solid electrolytes; examples include LiBH4, Li4(BH4)3I, and 3LiBH4-LiCl.

[0125] The inorganic solid electrolyte is preferably a particle. There is no particular limitation on the average particle size (volume average particle size) of the inorganic solid electrolyte, but it is preferably 0.01 μm or more, more preferably 0.1 μm or more. As an upper limit, it is preferably 100 μm or less, more preferably 50 μm or less.

[0126] The particle size of the inorganic solid electrolyte was determined using the following steps. A 1% (w / w) dispersion of the inorganic solid electrolyte particles was prepared by diluting the particles with water (or heptane in the case of substances unstable in water) in a 20 mL sample vial. The diluted dispersion sample was irradiated with ultrasound at 1 kHz for 10 minutes and then immediately used in the test. Using this dispersion sample, 50 data acquisitions were performed using a laser diffraction / scattering particle size distribution measuring device LA-920 (trade name, manufactured by HORIBA, Ltd.) at 25°C using a measuring quartz cell to obtain the volume average particle size. Other detailed conditions were described in JIS Z8828:2013 "Particle Size Analysis - Dynamic Light Scattering Method" as needed. Five samples were prepared for each grade, and their average value was used.

[0127] Inorganic solid electrolytes may contain one or more types.

[0128] In the case of forming a solid electrolyte layer, the per unit area (cm²) of the solid electrolyte layer 2 There are no particular limitations on the mass (mg) (weight per unit area) of the inorganic solid electrolyte. It can be appropriately determined based on the designed battery capacity; for example, it can be set to 1–100 mg / cm³. 2 .

[0129] In the case where the inorganic solid electrolyte composition contains the active substance described later, the total amount of the active substance and the inorganic solid electrolyte is preferably within the above range regarding the unit area weight of the inorganic solid electrolyte.

[0130] There is no particular limitation on the content of inorganic solid electrolyte in the inorganic solid electrolyte composition. From the viewpoint of adhesion, and further from the viewpoint of dispersibility, it is preferable that the solid content is 50% by mass or more, more preferably 70% by mass or more, and especially preferably 90% by mass or more out of 100% by mass. As an upper limit, from the same viewpoint, it is preferable that it is 99.9% by mass or less, more preferably 99.5% by mass or less, and especially preferably 99% by mass or less.

[0131] However, when the inorganic solid electrolyte composition contains the active substance described later, the total content of the active substance and the inorganic solid electrolyte in the inorganic solid electrolyte composition is preferably within the range described above.

[0132] In this invention, solid components refer to those components that, when dried at 150°C for 6 hours under a nitrogen atmosphere and at a pressure of 1 mmHg, volatilize or evaporate without disappearing. Typically, this refers to components other than the dispersion medium described later.

[0133] <Polymer Adhesives>

[0134] The polymer binder used in the inorganic solid electrolyte composition of the present invention is a binder formed by comprising a polymer, which exhibits solubility and dissolution in the dispersion medium contained in the inorganic solid electrolyte composition. By using this polymer binder in combination with solid particles such as inorganic solid electrolytes and metal-containing compounds described later, the dispersion stability and processability of the inorganic solid electrolyte composition (slurry) can be improved, thereby enabling the production of a low-resistivity constituent layer.

[0135] In this invention, the dissolution of a polymeric adhesive (also referred to as an adhesive) in a dispersion medium means, but is not limited to, all polymeric adhesives dissolved in a dispersion medium, for example, a solubility of 80% or more relative to the dispersion medium. The method for determining solubility is described below.

[0136] Specifically, a predetermined amount of the adhesive to be tested was weighed into a glass bottle, and 100g of a dispersion medium of the same type as that contained in the inorganic solid electrolyte composition was added. The mixture was stirred for 24 hours at 80 rpm on a mixing rotor at 25°C. The transmittance of the mixture obtained after 24 hours of stirring was determined under the following conditions. This test (transmittance determination) was performed by varying the amount of adhesive dissolved (the predetermined amount mentioned above), and the upper limit concentration X (mass%) of 99.8% transmittance was defined as the solubility of the adhesive in the dispersion medium.

[0137] -Transmittance Measurement Conditions-

[0138] Dynamic light scattering (DLS) measurement

[0139] Apparatus: DLS-8000 DLS measuring device manufactured by Otsuka Electronics Co., Ltd.

[0140] Laser wavelength and output: 488nm / 100mW

[0141] Sample cell: NMR tube

[0142] (Polymers that form polymeric adhesives)

[0143] The polymer forming the polymer binder (also called the binder-forming polymer) is not particularly limited as long as it is a polymer dissolved in the dispersion medium, and various polymers commonly used in the constituent layers of all-solid-state secondary batteries can be used. Among them, polymers having at least one bond selected from urethane bonds, urea bonds, amide bonds, imide bonds and ester bonds in the main chain (step-growth polymers) or polymer chains having carbon-carbon double bonds in the main chain (chain polymers) are preferred examples.

[0144] In this invention, the polymer backbone refers to all other molecular chains constituting the polymer that can be considered branched or comb-like linear molecular chains relative to the backbone. While the weight-average molecular weight depends on the molecular chains considered branched or comb-like, typically the longest chain constituting the polymer becomes the backbone. However, terminal groups present at the ends of the polymer are not included in the backbone. Furthermore, polymer side chains refer to molecular chains other than the backbone, including both short and long molecular chains.

[0145] The aforementioned bonds are not particularly limited as long as they are included in the polymer backbone. They can be any form contained in the constituent units (repeating units) and / or contained as bonds connecting different constituent units to each other. Furthermore, the bonds contained in the backbone are not limited to one type; they can be two or more types, preferably one to six types, and more preferably one to four types. In this case, the bonding mode of the backbone is not particularly limited; it can randomly have two or more types of bonds, or it can be a partitioned backbone with partitions of specific bonds and partitions of other bonds.

[0146] Polymers that have urethane bonds, urea bonds, amide bonds, imide bonds, or ester bonds in their main chain, as mentioned above, include, for example, step-growth polymers (condensation, addition, or addition condensation) such as polyurethane, polyurea, polyamide, polyimide, and polyester, or copolymers thereof. The copolymer can be a block copolymer in which the aforementioned polymers are used as chain segments, or a random copolymer formed by the random bonding of the constituent components of two or more of the aforementioned polymers.

[0147] Examples of chain polymers with carbon-carbon double bonds in their main chain include fluoropolymers, hydrocarbon polymers, ethylene polymers, and (meth)acrylic acid polymers. When a chain polymer is a copolymer, it can be a block copolymer or a random copolymer.

[0148] The adhesive can form one or more polymers.

[0149] The binder-forming polymer is a polymer that interacts with a metal-containing compound during the film-forming process of an inorganic solid electrolyte composition. Specifically, it is a polymer capable of receiving metal ions from the metal-containing compound (described later) (through chemical reaction, chemical or physical adsorption, etc.). Thus, the polymer binder can receive metal ions generated from the metal-containing compound, thereby imparting the aforementioned effects to the polymer binder. There are no particular limitations on the part of the structure that interacts with or receives metal ions, as long as these effects or receptions are achieved; examples include the chemical structure of the main chain (e.g., the bonds described above) and the functional group (a) described later.

[0150] The adhesive forming polymer preferably contains, for example, a component having a functional group (a) selected from the functional group (A) below as a substituent. When forming a film containing an inorganic solid electrolyte composition, the component having the functional group (a) can preferentially accept metal ions from a metal-containing compound, for example, through a salt exchange reaction, thereby forming a metal salt or the like with the functional group (a). The polymer adhesive having a metal chloride functional group (a) is cured into particles while adsorbing solid particles. A single component may have one or more functional groups (a), and the number is not particularly limited.

[0151] <Functional Groups (A)>

[0152] Hydroxyl, amino, carboxyl, sulfonyl (sulfonic acid group: -SO3H), phosphoric acid (phosphoryl group: -OPO(OH)2), phosphonic acid (-PO(OH)2), thioalkyl, heterocyclic, carboxylic anhydride (carboxylic anhydride group)

[0153] There are no particular limitations on the functional groups included in functional group (A), but they have the same meaning as the corresponding groups of substituent Z described later. Preferably, the amino group is -NH2, and the group corresponding to substituent Z has an R... P At that time, R P More preferably, hydrogen atoms. Each functional group can form a salt. The hydroxyl group does not contain the -OH group found in acid groups such as carboxyl groups. The carboxylic anhydride group contained in functional group (A) is not particularly limited and has the same meaning as the carboxylic anhydride group contained in functional group (B) described later, and the preferred range is also the same.

[0154] From the viewpoint that the functional groups contained in functional group (A) are particularly prone to salt exchange reactions with compounds containing metal elements, groups with active hydrogen atoms such as hydroxyl, carboxyl, sulfonyl, phosphoric acid, phosphonic acid, and thioalkyl are preferred, and acid groups such as carboxyl, sulfonyl, phosphoric acid, and phosphonic acid are more preferred, and carboxyl is even more preferred.

[0155] There is no particular limitation on the negative common logarithm [pKa] of the acid dissociation constant of each functional group contained in functional group (A). However, from the viewpoint of effectively exhibiting the interaction with metal-containing compounds, such as the rapid progress of salt exchange reactions and acceptance of metal ions, it is preferred to be -2.0 to 8.0, more preferably -1.0 to 6.0, even more preferably 0.0 to 4.0, and especially preferably 0.0 to 2.0.

[0156] In this invention, pKa is defined as the value (in water) determined by neutralization titration using an automatic potentiometric titration apparatus (trade name: Titrando 905, manufactured by Metrohm Japan Ltd.).

[0157] When the adhesive forming polymer has multiple functional groups (a), the pKa of each functional group must be at least the lowest value and be included in the above range. The pKa of other functional groups may or may not be included in the above range.

[0158] Functional group (a) can be incorporated into the main chain of a polymer or into the side chain.

[0159] When incorporated into a side chain, it includes atoms that are directly bonded to or via a linker group of the polymer main chain. Examples of linkers that can be used to bond the functional group (a) and the main chain include alkylene groups (preferably 1-12 carbon atoms, more preferably 1-6, even more preferably 1-3), alkenyl groups (preferably 2-6 carbon atoms, more preferably 2-3), aryl groups (preferably 6-24 carbon atoms, more preferably 6-10), oxygen atoms, sulfur atoms, and imino groups (-NR). N -:R N This refers to a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms, a carbonyl group, a phosphate linker (-OP(OH)(O)-O-), a phosphonic acid linker (-P(OH)(O)-O-), or a group related to combinations thereof. Preferably, the linker is a group composed of an alkylene group, an arylene group, a carbonyl group, an oxygen atom, a sulfur atom, and an imino group.

[0160] In this invention, the number of atoms constituting the linking group is preferably 1 to 36, more preferably 1 to 24, even more preferably 1 to 12, and particularly preferably 1 to 6. The number of linking atoms in the linking group is preferably 10 or less, more preferably 8 or less. A lower limit is 1 or more. The above-mentioned number of linking atoms refers to the minimum number of atoms connecting the defined structural parts. For example, in the case of -CH2-C(=O)-O-, the number of atoms constituting the linking group is 6, but the number of linking atoms is 3.

[0161] Furthermore, when functional group (a) is incorporated into the side chain, in addition to the bonding via the aforementioned linker, it also includes the presence of functional group (a) on the polymer chain of the macromonomer constituting the side chain. Such macromonomer can be appropriately determined based on the type of main chain of the polymer formed by the adhesive, and is not unique; for example, macromonomers with polymer chains of chain polymers described later can be cited.

[0162] The functional groups contained in functional group (A) are used for interaction with compounds containing metal elements, but a portion of them can be used as functional group (b) described later for interaction with solid particles.

[0163] The constituent components having functional group (a) are not particularly limited as long as they can form the constituent components of the adhesive polymer, and can be appropriately selected according to the type and composition of the adhesive polymer.

[0164] The content of the constituent having the aforementioned functional group (a) in the adhesive forming polymer (all constituents) is not particularly limited. From the viewpoint of exhibiting sufficient interaction with the metal-containing compound, it is preferably 0.1 to 10 mol%, more preferably 0.1 to 5 mol%, and even more preferably 0.2 to 4.0 mol%. When the adhesive forming polymer contains multiple constituents having functional groups (a), the content of the constituent having functional groups (a) is defined as the total content. Furthermore, when a constituent has multiple functional groups (a), the content of the constituent having functional groups (a) usually refers to the content of that constituent. However, in this invention, based on the relationship between the interaction with the metal-containing compound and the adhesive strength with solid particles, it is defined as the total content of each functional group. Where multiple functional groups (a) exist in one molecular chain (when derived from a common raw material compound), the above total content does not include the content of each functional group (a), and the multiple functional groups are summarized as one functional group and included in the total content.

[0165] The adhesive-forming polymer preferably contains, for example, a component having a functional group (b) selected from the functional group (B) below as a substituent. The component having functional group (b) has the function of enhancing the adsorption force of the polymer adhesive on solid particles. The polymer adhesive preferably adsorbs onto solid particles through physical or chemical actions (chemical bond formation, electron donation and acceptance, etc.). The functional group (b) can be incorporated into the polymer backbone or into the side chain. When incorporated into the side chain, it includes bonding directly to or via a linker to the atoms forming the polymer backbone. There are no particular limitations on the linker used to bond the functional group (b) and the backbone; for example, a linker that bonds the aforementioned functional group (a) and the backbone is preferably used. Furthermore, it also includes incorporating the functional group (b) as a substituent into the polymer chain of the macromonomer constituting the side chain. The macromonomer used to incorporate the macromonomer constituting the side chain can be appropriately determined according to the type of the adhesive-forming polymer backbone, and is not unique; for example, macromonomers with polymer chains of chain polymers described later can be used. A constituent component may have one or more functional groups (b). When it has two or more functional groups, they may or may not bond with each other.

[0166] <Functional Groups (B)>

[0167] Hydroxyl, amino, carboxyl, sulfonyl, phosphate, phosphonic acid, thioalkyl, ether (-O-), imino (=NR, -NR-), ester (-CO-O-), amide (-CO-NR-), carbamate (-NR-CO-O-), urea (-NR-CO-NR-), heterocyclic, aryl, carboxylic anhydride, fluoroalkyl, siloxane

[0168] The amino, sulfonyl, phosphate, heterocyclic, and aryl groups included in functional group (B) are not particularly limited and have the same meaning as the corresponding groups of substituent Z described later. The amino group preferably has 0 to 12 carbon atoms, more preferably 0 to 6, and especially preferably 0 to 2. When amino, ether, imino (-NR-), ester, amide, carbamate, or urea bonds are included in a ring structure, it is classified as a heterocycle.

[0169] Hydroxyl, amino, carboxyl, sulfonyl, phosphate, phosphonic acid, and thioalkyl groups can form salts.

[0170] A fluoroalkyl group is an alkyl group or a group obtained by substituting at least one hydrogen atom in a cycloalkyl group with a fluorine atom, preferably having 1 to 20 carbon atoms, more preferably 2 to 15, and even more preferably 3 to 10. The number of fluorine atoms on the carbon atoms can be part of the substituted hydrogen atoms or all of them (perfluoroalkyl).

[0171] There are no particular limitations on the siloxane group; for example, it is preferred to have a siloxane group consisting of -(SiR2-O).n - indicates the structural group. The repetition number n is preferably an integer from 1 to 100, more preferably an integer from 5 to 50, and even more preferably an integer from 10 to 30.

[0172] R in each bond or group represents a hydrogen atom or a substituent, preferably a hydrogen atom. There are no particular restrictions on the substituents, which are selected from the substituent Z described later, and are preferably alkyl.

[0173] There are no particular limitations on the carboxylic anhydride group, including groups formed by removing one or more hydrogen atoms from a carboxylic anhydride (e.g., groups represented by formula (2a) below), and constituent components formed by copolymerizing polymerizable carboxylic anhydrides as copolymerizable compounds (e.g., constituent components represented by formula (2b) below). As groups formed by removing one or more hydrogen atoms from a carboxylic anhydride, groups formed by removing one or more hydrogen atoms from a cyclic carboxylic anhydride are preferred. Carboxylic anhydride groups derived from cyclic carboxylic anhydrides are also equivalent to heterocyclic groups, but are classified as carboxylic anhydride groups in this invention. Examples of carboxylic anhydride groups include, for example, acyclic carboxylic anhydrides such as acetic anhydride, propionic anhydride, and benzoic acid rod, and cyclic carboxylic anhydrides such as maleic anhydride, phthalic anhydride, fumaric acid rod, succinic anhydride, and itaconic anhydride. There are no particular limitations on the polymerizable carboxylic anhydride, and carboxylic anhydrides having unsaturated bonds within the molecule can be cited, with polymerizable cyclic carboxylic anhydrides being preferred. Specifically, maleic anhydride and itaconic anhydride are examples.

[0174] Examples of carboxylic anhydride groups include groups represented by formula (2a) or constituents represented by formula (2b), but the invention is not limited to these. In each formula, * indicates a bonding position.

[0175] [Chemical Formula 1]

[0176]

[0177] In stepwise polymer polymerization, when the chemical structure of the polymer is represented by components derived from the starting material compounds, ester bonds (-CO-O-), amide bonds (-CO-NR-), urethane bonds (-NR-CO-O-), and urea bonds (-NR-CO-NR-) are respectively represented by -CO- and -O- groups, -CO- and -NR- groups, -NR-CO- and -O- groups, and -NR-CO- and -NR- groups. Therefore, in this invention, components having these bonds are designated as components derived from carboxylic acid compounds or isocyanate compounds, regardless of the polymer's labeling, and do not include components derived from polyols or polyamines.

[0178] Furthermore, in chain polymers, components with ester bonds (excluding ester bonds that form carboxyl groups) or amide bonds refer to components whose ester bonds or amide bonds are not directly bonded to the atoms constituting the main chain, for example, components that do not contain components derived from alkyl methacrylates.

[0179] The constituent components having functional group (b) are not particularly limited as long as they can form the constituent components of the adhesive polymer, and can be appropriately selected according to the type and composition of the adhesive polymer.

[0180] The content of the component having functional group (b) in the adhesive forming polymer (all components) is not particularly limited, but from the viewpoint of the adhesiveness of solid particles, it is preferably 1 to 90 mol%, more preferably 20 to 87 mol%, and even more preferably 30 to 85 mol%. When the adhesive forming polymer contains multiple components having functional group (b), the content of the component having functional group (b) is set as the total amount. Furthermore, when one component has multiple functional groups (b), the content of the component having functional group (b) is set as the total amount calculated in the same way as when one component has multiple functional groups (a).

[0181] Furthermore, when functional group (b) also corresponds to functional group (a), the content of the constituent having functional group (b) is set to the content of the constituent having functional group (a) from the viewpoint of exhibiting interaction with the metal-containing compound. However, from the viewpoint of further achieving the cohesiveness of solid particles, it is preferable to set it to the content of the constituent having functional group (b).

[0182] -Step-growth polymer-

[0183] Examples of stepwise polymeric polymers (condensation, addition, or addition condensation) that form polymers as binders include polyurethanes, polyureas, polyamides, polyimides, polyesters, polyethers, and polycarbonates, with polyurethanes, polyureas, polyamides, polyimides, or polyesters being preferred. The stepwise polymeric polymer preferably has components containing the aforementioned functional group (a) or functional group (b).

[0184] Polymers such as polyurethane, polyurea, polyamide, and polyimide, which can be used as step-polymers, include, for example, polymers with hard and soft segments (polymer adhesive (B)) described in Japanese Patent Application Publication No. 2015-088480 and polymers described in International Patent Application Publication No. 2015 / 046313, which are obtained by introducing constituent components having functional groups (a) or functional groups (b).

[0185] There are no particular limitations on the methods for incorporating functional groups. Examples include copolymerizing compounds having functional groups selected from functional group (A) or functional group (B), using a polymerization initiator having (generating) the aforementioned functional groups, and utilizing polymer reactions. Furthermore, functional groups can be introduced by using side chains or terminal groups present in the adhesive-forming polymer as reaction sites. For example, as shown in the examples described later, functional groups (a) can be introduced by using compounds having functional groups, through reactions with alkenes containing double bonds remaining in the adhesive-forming polymer, alkene-thiols reactions, and various reactions with carboxylic anhydride groups (carboxylic anhydride groups).

[0186] There are no particular limitations on the compounds having the aforementioned functional groups. Examples include compounds having at least one carbon-carbon unsaturated bond and the aforementioned functional group. Examples include compounds formed by direct bonding of a carbon-carbon unsaturated bond to the aforementioned functional group, compounds formed by bonding a carbon-carbon unsaturated bond to the aforementioned functional group via the aforementioned linker, and compounds in which the functional group itself contains a carbon-carbon unsaturated bond (e.g., the aforementioned polymeric cyclic carboxylic anhydride). Furthermore, compounds having the aforementioned functional groups include compounds capable of incorporating the functional group into the constituent components of the adhesive-forming polymer through various reactions (e.g., compounds (including polymers) capable of undergoing addition or condensation reactions with constituent components derived from carboxylic anhydrides, constituent components having carbon-carbon unsaturated bonds, etc.). In addition, compounds having the aforementioned functional groups also include compounds formed by direct or via the aforementioned linker where a carbon-carbon unsaturated bond is bonded to a macromonomer in the polymer chain as a substituent. The macromonomer used as a component of the introduced macromonomer can be appropriately determined according to the type of main chain of the polymer formed by the adhesive, and is not unique. For example, macromonomers with polymer chains that have polymer chains can be mentioned later.

[0187] The number-average molecular weight of the macromonomer is not particularly limited, but from the viewpoint of maintaining excellent dispersion stability and processability while making the solid particles more cohesive and the adhesion to the current collector stronger, it is preferably 500 to 100,000, more preferably 1,000 to 50,000, and even more preferably 2,000 to 20,000. Furthermore, the content of repeating units having functional groups (b) incorporated into the macromonomer is preferably 1 to 100 mol%, more preferably 3 to 80 mol%, and even more preferably 5 to 70 mol%. The content of repeating units without functional groups (b) is preferably 0 to 90 mol%, more preferably 0 to 70 mol%, and even more preferably 0 to 50 mol%. From the viewpoint of solubility, any component can be selected.

[0188] -Chain polymer-

[0189] Examples of chain polymers that form adhesive polymers include fluoropolymers, hydrocarbon polymers, ethylene polymers, and (meth)acrylic acid polymers, with ethylene polymers, hydrocarbon polymers, or (meth)acrylic acid polymers being preferred. The chain polymer as a constituent component preferably has a constituent component containing the aforementioned functional group (a) or functional group (b).

[0190] There are no particular limitations on the fluoropolymers used; examples include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), copolymers of PVdF and hexafluoropropylene (PVdF-HFP), and copolymers of PVdF, hexafluoropropylene, and tetrafluoroethylene (PVdF-HFP-TFE). In PVdF-HFP, the copolymerization ratio of PVdF to HFP [PVdF:HFP] (mass ratio) is not particularly limited, but is preferably 9:1 to 5:5, and more preferably 9:1 to 7:3 from the viewpoint of adhesion. In PVdF-HFP-TFE, the copolymerization ratio of PVdF to HFP and TFE [PVdF:HFP:TFE] (mass ratio) is not particularly limited, but is preferably 20 to 60:10 to 40:5 to 30.

[0191] There are no particular limitations on hydrocarbon polymers, for example polyethylene, polypropylene, polyethylene-poly(ethylene-butene)-polyethylene copolymer, natural rubber, polybutadiene, polyisoprene, polystyrene, polystyrene-butadiene copolymer, polypropylene-polyethylene-polybutene copolymer (CEBC), styrene-based thermoplastic elastomers, polybutene, acrylonitrile-butadiene copolymer, or their hydrogenated (hydrogenated) polymers. There are no particular limitations on the styrene-based thermoplastic elastomers or their hydrogenated derivatives. Examples include styrene-ethylene-butene-styrene block copolymers (SEBS), styrene-isoprene-styrene block copolymers (SIS), hydrogenated SIS, styrene-isobutene-styrene block copolymers (SIBS), styrene-butadiene-styrene block copolymers (SBS), hydrogenated SBS, styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber (HSBR), and random copolymers corresponding to the aforementioned block copolymers, such as SEBS. In this invention, the preferred feature of the hydrocarbon polymer is that polymers without unsaturated groups (e.g., 1,2-butadiene components) bonded to the main chain can suppress the formation of chemical crosslinks.

[0192] Hydrocarbon polymers may have functional groups (b) selected from functional group (B), such as fluoroalkyl and siloxane, on their side chains. This is because the adsorption force relative to solid particles can be appropriately tuned.

[0193] There are no particular limitations on the type of vinyl polymer; for example, polymers containing 50 mol% or more of vinyl monomers other than (meth)acrylic acid compound (M1) can be cited. Vinyl compounds, which will be described later, can be cited as vinyl monomers. Specifically, examples of vinyl polymers include polyvinyl alcohol, polyvinyl acetal, polyvinyl acetate, or copolymers containing these.

[0194] The vinyl polymer preferably contains, in addition to components derived from vinyl monomers, components derived from (meth)acrylic acid compound (M1) that form the (meth)acrylic acid polymer described later, and further components derived from macromonomers (MM). The content of components derived from vinyl monomers is preferably the same as the content of components derived from (meth)acrylic acid compound (M1) in the (meth)acrylic acid polymer. The content of components derived from (meth)acrylic acid compound (M1) in the polymer is not particularly limited as long as it is less than 50 mol%, preferably 0-40 mol%, more preferably 5-35 mol%. The content of component (MM) is preferably the same as the content in the (meth)acrylic acid polymer.

[0195] There are no particular limitations on the (meth)acrylic acid polymer. For example, polymers obtained by (co)polymerization of at least one (meth)acrylic acid compound (M1) selected from (meth)acrylic acid compounds, (meth)acrylic ester compounds, (meth)acrylamide compounds, and (meth)acrylonitrile compounds are preferred. Furthermore, (meth)acrylic acid polymers composed of copolymers of (meth)acrylic acid compound (M1) and other polymerizable compounds (M2) are also preferred. There are no particular limitations on other polymerizable compounds (M2), and examples include vinyl compounds such as styrene compounds, vinylnaphthalene compounds, vinylcarbazole compounds, allyl compounds, vinyl ether compounds, vinyl ester compounds, itaconic acid dialkyl compounds, and unsaturated carboxylic anhydrides. Examples of vinyl compounds include, for example, the "ethylene monomers" described in Japanese Patent Application Publication No. 2015-88486.

[0196] There are no particular restrictions on the content of other polymeric compounds (M2) in (meth)acrylic acid polymers, for example, it can be set to less than 50 mol%.

[0197] As a (meth)acrylic acid polymer, the polymer described in Japanese Patent No. 6295332 can be cited as an example.

[0198] Chain-polymers can be categorized as polymers obtained by introducing constituents having functional groups (a) or (b) into the aforementioned polymers. The method of incorporating functional groups is the same as that for step-growth polymers.

[0199] The adhesive forming polymer (each component and raw material compound) may have substituents. As a substituent, there are no particular restrictions as long as it is a group other than the functional groups included in the functional groups (A) and (B) described above, but groups selected from the substituents Z below are preferred.

[0200] -Substituent Z-

[0201] Examples of alkyl groups include alkyl groups (preferably alkyl groups with 1 to 20 carbon atoms, such as methyl, ethyl, isopropyl, tert-butyl, pentyl, heptyl, 1-ethylpentyl, benzyl, 2-ethoxyethyl, 1-carboxymethyl, etc.), alkenyl groups (preferably alkenyl groups with 2 to 20 carbon atoms, such as vinyl, allyl, oleyl, etc.), alkynyl groups (preferably alkynyl groups with 2 to 20 carbon atoms, such as ethynyl, butyrynyl, phenylethynyl, etc.), and cycloalkyl groups (preferably cycloalkyl groups with 3 to 20 carbon atoms, such as cyclopropyl, cyclopentyl, cyclohexyl, 4-methylcyclohexyl, etc.). In this specification, when the alkyl group is used... The term "[]" usually indicates the presence of a cycloalkyl group, but is described separately here. It includes aryl (preferably an aryl group with 6 to 26 carbon atoms, such as phenyl, 1-naphthyl, 4-methoxyphenyl, 2-chlorophenyl, 3-methylphenyl, etc.), aralkyl (preferably an aralkyl group with 7 to 23 carbon atoms, such as benzyl, phenethyl, etc.), and heterocyclic (preferably a heterocyclic group with 2 to 20 carbon atoms, more preferably a heterocyclic group having at least one oxygen atom, sulfur atom, and nitrogen atom in a 5- or 6-membered ring). Heterocyclic groups include aromatic heterocyclic groups and aliphatic heterocyclic groups. For example, tetrahydropyran cycloyl, tetrahydrofuran cycloyl, 2-pyranyl... The following groups are included: pyridyl, 4-pyridyl, 2-imidazolyl, 2-benzimidazolyl, 2-thiazolyl, 2-oxazolyl, pyrrolidone, etc.); alkoxy groups (preferably alkoxy groups with 1 to 20 carbon atoms, such as methoxy, ethoxy, isopropoxy, benzyloxy, etc.); aryloxy groups (preferably aryloxy groups with 6 to 26 carbon atoms, such as phenoxy, 1-naphthoxy, 3-methylphenoxy, 4-methoxyphenoxy, etc.; when referred to as aryloxy in this specification, it refers to a group containing an aryloxy group); heterocyclic oxy groups (groups with a -O- group bonded to the above heterocyclic groups); alkoxycarbonyl groups (preferably groups with 2 to 20 carbon atoms). Alkoxycarbonyl (e.g., ethoxycarbonyl, 2-ethylhexyloxycarbonyl, dodecyloxycarbonyl, etc.), aryloxycarbonyl (preferably aryloxycarbonyl with 6 to 26 carbon atoms, e.g., phenoxycarbonyl, 1-naphthoxycarbonyl, 3-methylphenoxycarbonyl, 4-methoxyphenoxycarbonyl, etc.), amino (preferably containing amino, alkylamino, or arylamino with 0 to 20 carbon atoms, e.g., amino(-NH2), N,N-dimethylamino, N,N-diethylamino, N-ethylamino, aniline, etc.), aminosulfonyl (preferably aminosulfonyl with 0 to 20 carbon atoms, e.g., N,N-dimethylaminosulfonyl, N-phenylaminosulfonyl, etc.), acyl groups (including alkyl carbonyl, alkenyl carbonyl, alkynyl carbonyl, aryl carbonyl, heterocyclic carbonyl, preferably acyl groups with 1 to 20 carbon atoms, such as acetyl, propionyl, butyryl, octanoyl, hexadecanoyl, acryl, methacryl, crotonyl, benzoyl, naphthoyl, nicotinyl, etc.), acyloxy groups (including alkyl carbonyloxy, alkenyl carbonyloxy, alkynyl carbonyloxy, aryl carbonyloxy, heterocyclic carbonyloxy, preferably acyloxy groups with 1 to 20 carbon atoms, such as acetyloxy, propionyloxy, butyryloxy, octanoyloxy). Hexadecyloxy, acryloyloxy, methacryloyloxy, crotonyloxy, benzoyloxy, naphthyloxy, nicotinoxy, etc.), aromatic acryloyloxy (preferably aromatic acryloyloxy with 7 to 23 carbon atoms, such as benzoyloxy), carbamoyl (preferably carbamoyl with 1 to 20 carbon atoms, such as N,N-dimethylcarbamoyl, N-phenylcarbamoyl), amide (preferably amide with 1 to 20 carbon atoms, such as acetamido, benzoylamino, etc.), alkylthio (preferably alkylthio with 1 to 20 carbon atoms, such as methylthio, ethylthio, isopropylthio). , benzyl thioyl, etc.), aryl thioyl (preferably aryl thioyl with 6 to 26 carbon atoms, for example, phenylthioyl, 1-naphthioyl, 3-methylphenylthioyl, 4-methoxyphenylthioyl, etc.), heterocyclic thioyl (a group with -S- group bonded to the above heterocyclic group), alkyl sulfonyl (preferably alkyl sulfonyl with 1 to 20 carbon atoms, for example, methyl sulfonyl, ethyl sulfonyl, etc.), aryl sulfonyl (preferably aryl sulfonyl with 6 to 22 carbon atoms, for example, benzyl sulfonyl, etc.), alkylsilyl (preferably alkylsilyl with 1 to 20 carbon atoms, for example, monomethylsilyl, dimethylsilyl) Trimethylsilyl, triethylsilyl, etc.), arylsilyl (preferably arylsilyl with 6 to 42 carbon atoms, such as triphenylsilyl), alkoxysilyl (preferably alkoxysilyl with 1 to 20 carbon atoms, such as monomethoxysilyl, dimethoxysilyl, trimethoxysilyl, triethoxysilyl, etc.), aryloxysilyl (preferably aryloxysilyl with 6 to 42 carbon atoms, such as triphenoxysilyl), phosphoryl (preferably phosphoric acid with 0 to 20 carbon atoms, such as -OP(=O)(R, P )2) Phosphonyl group (preferably a phosphonyl group with 0 to 20 carbon atoms, for example, -P(=O)(R P )2) Oxyphosphin group (preferably oxyphosphin group with 0 to 20 carbon atoms, for example, -P(R P 2) Phosphonic acid group (preferably a phosphonic acid group with 0 to 20 carbon atoms, for example, -PO(OR) P 2) Sulfonate group (sulfonic acid group, -SO3R) P), carboxyl, hydroxyl, thioalkyl, cyano, halogen atoms (e.g., fluorine, chlorine, bromine, iodine, etc.). R P It is a hydrogen atom or a substituent (preferably a group selected from substituent Z).

[0202] Furthermore, each of the groups listed in these substituents Z can be further replaced by the aforementioned substituents Z.

[0203] The aforementioned alkyl, alkylene, alkenyl, alkenylene, ynyl and / or ynylene groups can be cyclic or chain-like, and can be straight-chain or branched.

[0204] (Polymer adhesives or the physical properties or characteristics of polymers formed by adhesives, etc.)

[0205] The polymer adhesive or adhesive-formed polymer described above preferably has the following physical properties or characteristics.

[0206] The moisture concentration of the polymer binder (polymer) is preferably below 100 ppm (by mass). Furthermore, this polymer binder can either crystallize and dry the polymer, or be used directly as a polymer binder dispersion.

[0207] The binder-forming polymer is preferably amorphous. In this invention, "amorphous" typically means that no endothermic peak due to crystal melting is observed when measured at the glass transition temperature.

[0208] The binder-forming polymer can be either a non-crosslinked polymer or a crosslinked polymer. Furthermore, when the polymer is crosslinked by heating or applying voltage, the molecular weight can be greater than the aforementioned molecular weight. Preferably, when starting to use an all-solid-state secondary battery, the mass-average molecular weight of the polymer is within the range described later.

[0209] There is no particular limitation on the mass-average molecular weight of the polymer formed by the adhesive. For example, it is preferably 15,000 or more, more preferably 30,000 or more, and even more preferably 50,000 or more. As an upper limit, it is practically 5,000,000 or less, preferably 4,000,000 or less, and more preferably 3,000,000 or less.

[0210] -Determination of molecular weight-

[0211] In this invention, the molecular weight of polymers, polymer chains, and macromonomers, unless otherwise specified, refers to the mass-average molecular weight or number-average molecular weight converted from standard polystyrene obtained by gel permeation chromatography (GPC). The determination method is generally set to the value determined by the method described in either condition 1 or condition 2 (preferred). A suitable eluent is selected and used according to the type of polymer or macromonomer.

[0212] (Condition 1)

[0213] Column: Connects 2 TOSOH TSKgel Super AWM-H (trade name, manufactured by TOSOH CORPORATION)

[0214] Charge carriers: 10 mM LiBr / N-methylpyrrolidone

[0215] Temperature measured: 40℃

[0216] Carrier flow rate: 1.0 ml / min

[0217] Sample concentration: 0.1% by mass

[0218] Detector: RI (Refractive Index) Detector

[0219] (Condition 2)

[0220] Tubes: Tubes connected to TOSOH TSKgel Super HZM-H, TOSOH TSKgel Super HZ4000, and TOSOH TSKgel Super HZ2000 (all trade names, manufactured by Tosoh Corporation) are used.

[0221] Support: Tetrahydrofuran

[0222] Temperature measured: 40℃

[0223] Carrier flow rate: 1.0 ml / min

[0224] Sample concentration: 0.1% by mass

[0225] Detector: RI (Refractive Index) Detector

[0226] The inorganic solid electrolyte composition of the present invention may contain one polymer binder or two or more polymer binders.

[0227] There is no particular limitation on the total content of the polymer binder in the inorganic solid electrolyte composition. From the viewpoint of improving dispersion stability and processability, and thus exhibiting sufficient adhesion, it is preferably 0.1 to 10.0% by mass of the solid component, more preferably 0.2 to 8% by mass, even more preferably 0.3 to 6% by mass, and particularly preferably 0.5 to 3% by mass.

[0228] In this invention, the mass ratio of the total mass (total amount) of the inorganic solid electrolyte and the active material to the total mass of the polymer binder [(mass of inorganic solid electrolyte + mass of active material) / (total mass of polymer binder)] in 100% by mass of the solid component is preferably in the range of 1,000 to 1. Furthermore, this ratio is more preferably 500 to 2, and even more preferably 100 to 10.

[0229] <Compounds Containing Metal Elements>

[0230] The inorganic solid electrolyte composition of the present invention contains a metal-containing compound. By allowing the metal-containing compound to coexist with the inorganic solid electrolyte particles and the polymer binder in a solid state, it interacts with the polymer binder in a dissolved state, for example, starting from the metal-containing compound and the ion receiving portion of the metal element, thereby enabling the polymer binder to solidify into particles.

[0231] The metal-containing compound has the property of supplying at least a portion of the metal elements constituting the molecule as ions (cations) to the binder to form a polymer.

[0232] The ability of a metal-containing compound to supply metal ions is not solely determined by the chemical structure of the polymer formed by the binder, which is capable of accepting metal ions. For example, for the anion constituting the metal-containing compound, the negative common logarithm [pKa] (in water) of its conjugate acid's acid dissociation constant is preferably -2 to 40, more preferably -2 to 20, further preferably 0 to 10, and especially preferably 2 to 8. If the pKa of the conjugate acid is within the above range, the metal-containing compound can rapidly release and generate metal ions as cations, thereby effectively supplying them to the binder to form the polymer. The pKa of the conjugate acid can be determined in the same manner as the pKa of the functional group (a) described above.

[0233] From the viewpoint of improving dispersion characteristics and battery characteristics, the pKa of the conjugate acid from which the above-mentioned anion is derived is preferably greater than the pKa of the functional group (a) (when the binder forming polymer has multiple functional groups (a), at least the lowest pKa among the pKa values ​​of each functional group should be observed). In this case, the pKa difference between the pKa of the conjugate acid and the pKa of the functional group (a) [(pKa of the conjugate acid) - (pKa of the functional group)] is not particularly limited and can be set to 0.1 or more. However, from the viewpoint of achieving a high level of balance between dispersion characteristics and resistance, it is preferably 2 or more, and more preferably 2.5 or more. The upper limit of the pKa difference is not particularly limited; for example, it can be set to 35 or less, preferably 30 or less, and more preferably 20 or less.

[0234] If a metal-containing compound can release metal ions during the film-forming process of a film containing an inorganic solid electrolyte composition, then a portion of the metal element can also be released as ions outside of the film-forming process (during preparation, storage, etc.).

[0235] The metal-containing compound is insoluble in the dispersion medium contained in the inorganic solid electrolyte composition and exists in a solid state within the inorganic solid electrolyte composition. By existing in a solid state, even during film formation, the surface of the solid particles is only partially coated, and the increase in interfacial resistance between the solid particles can be suppressed. In this invention, insolubility means a solubility of 0.05% or less relative to the dispersion medium based on the above-described measurement method; a portion of the metal-containing compound can dissolve in the dispersion medium without impairing the effects of this invention.

[0236] In inorganic solid electrolyte compositions, the metal-containing compound is preferably dispersed in a solid state in the dispersion medium. Dispersing the metal-containing compound in a solid state in the dispersion medium means that, using a dispersion prepared by mixing (dispersing) the metal-containing compound with the dispersion medium at a solid content concentration of 10% by mass, the reduction in solid content in the dispersion stability test of the examples described later is less than 5% by mass.

[0237] The average particle size of the metal-containing compound existing in a solid state is not particularly limited and can be set to 0.05–35 μm. From the viewpoint of improving dispersion characteristics and battery characteristics, the lower limit of the average particle size is preferably 0.05 μm or more, more preferably 0.07 μm or more, and even more preferably 0.1 μm or more, and the upper limit of the average particle size is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 2 μm or less. The average particle size is a value measured by the method described in the examples below. The average particle size of the metal-containing compound can be adjusted, for example, by the compound structure, the type and content of anions or metal elements, the type of dispersion medium, etc.

[0238] There are no particular limitations on the type of compound containing a metal element, as long as it exhibits the property of being able to supply the aforementioned metal element ions; various compounds can be cited. The metal-containing compound can be an inorganic compound, preferably an organic compound, and can be a polymeric compound, preferably a low-molecular-weight compound (non-polymeric compound). Preferably, the metal-containing compound does not exhibit ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table (lithium-ion conductivity: less than 10). -6 S / cm).

[0239] The metal-containing compounds used in this invention are, from the viewpoint of exhibiting the ability to supply the aforementioned metal ions, for example, from the viewpoint of exhibiting the aforementioned pKa, are conjugate acids of anions with a pKa less than -2, and do not exhibit the ability to supply metal ions, and are typically used in all-solid-state secondary batteries, inorganic solid electrolytes, active materials, conductive additives, lithium salts, ionic liquids, and compounds different from thickeners.

[0240] As a metal-containing compound, an organometallic compound or organometallic salt is preferred, for example, to contain anions derived from organic compounds such as organic acids, alcohols, and hydrocarbons, and cations derived from a metal element. There are no particular limitations on the organometallic compound or organometallic salt; examples include organoacid metal salts containing anions derived from organic acids and cations derived from metal elements, alkoxides (alcohols) containing anions derived from alcohols and cations derived from metal elements, and organometallic compounds containing anions derived from hydrocarbons and cations derived from metal elements. Among these, organoacid metal salts or alkoxides are preferred, and organoacid metal salts are more preferred. Preferably, the pKa of the anion (the aforementioned organic compound) is within the aforementioned range.

[0241] There are no particular restrictions on the metal elements that form cations, and metal elements belonging to Groups 1 to 17 of the periodic table can be appropriately selected. However, from the viewpoint of improving dispersion characteristics and battery characteristics, it is preferable to include metal elements belonging to Groups 1, 2, 12 or 13 of the periodic table. More preferably, it includes metal elements belonging to Group 1 (alkali metals) or Group 2 (alkaline earth metals). It is even more preferable to include metal elements belonging to Group 1 of the periodic table, and especially preferably, it includes lithium.

[0242] There is no particular limitation on the valence that can be used as a metallic element or its ion. For example, it can be selected from the range of 1 to 7 valences. However, from the viewpoint of improving dispersion characteristics and battery characteristics, a smaller valence is preferred. For example, 1 to 3 valences are more preferred, 1 or 2 valences are even more preferred, and 1 valence is particularly preferred.

[0243] In the relationship with inorganic solid electrolytes, the metal element is preferably the same as the metal element contained in the inorganic solid electrolyte.

[0244] The organic compound that forms the anion is a compound in which a metal element in a compound containing a metal element is replaced by a hydrogen atom, and there are no particular restrictions. Among the above, organic acids, alcohols, and hydrocarbons are preferred, and organic acids are more preferred.

[0245] Organic acids are hydrocarbon compounds containing acid groups, such as organic carboxylic acids, organic sulfonic acids, organic phosphonic acids, and organic boric acids. From the viewpoint of achieving a high level of improvement in dispersion characteristics and low resistivity, organic carboxylic acids are preferred. The number of acid groups in an organic acid is not particularly limited, but is preferably 1 to 3, and more preferably 1 or 2.

[0246] There are no particular limitations on the hydrocarbon compounds constituting the organic acid. For example, chain or cyclic saturated hydrocarbons, chain or cyclic unsaturated hydrocarbons, or aromatic hydrocarbons are preferred, with chain saturated hydrocarbons being the most desirable. Furthermore, the structure of the chain saturated hydrocarbon or unsaturated hydrocarbon can be a straight chain or a branched chain. The aforementioned hydrocarbon compounds may have substituents selected from the substituents Z mentioned above.

[0247] There are no particular limitations on what constitutes an organic carboxylic acid; examples include saturated or unsaturated fatty acids, saturated or unsaturated aliphatic dicarboxylic acids, and aromatic dicarboxylic acids. Additionally, formic acid, a compound formed by one carboxyl group bonded to a hydrogen atom, and oxalic acid, a compound formed by two carboxyl groups bonded together, are both included in the category of organic carboxylic acids.

[0248] Alcohols are hydrocarbon compounds containing hydroxyl groups. The number of hydroxyl groups in a hydrocarbon compound is not particularly limited, but is preferably 1 to 3, more preferably 1 or 2. There are no particular limitations on the hydrocarbon compounds constituting alcohols; hydrocarbon compounds constituting organic acids are preferred examples.

[0249] There are no particular restrictions on the hydrocarbon compounds that form anions, but hydrocarbon compounds that constitute organic acids can be preferred examples.

[0250] There is no particular limitation on the number of carbon atoms in the organic compound that forms the anion, and it can be set to 1 to 24. However, from the viewpoint of improving dispersion characteristics and battery characteristics, it is preferable to have 3 to 22, more preferably 6 to 21, even more preferably 10 to 20, and especially preferably 12 to 19.

[0251] Metal-containing compounds can exist alone in compositions containing inorganic solid electrolytes, or they can form complexes with other components (e.g., adsorbates, complexes, solvates). In this case, the organocarboxylic acid metal salts, as in Patent Document 2, did not form boron trifluoride complexes.

[0252] The following examples and embodiments illustrate specific examples of compounds containing metal elements, but the present invention is not limited to these. Furthermore, compounds C-4 to C-26 are shown as lithium salts, but the invention is not limited to lithium salts.

[0253] [Chemical Formula 2]

[0254]

[0255] The inorganic solid electrolyte composition of the present invention may contain one metal element compound or two or more.

[0256] There is no particular limitation on the content of the metal element compound in the inorganic solid electrolyte composition. From the viewpoint of being able to simultaneously improve the dispersion characteristics and reduce the resistance, as well as to ensure sufficient adhesion of solid particles, the content of the solid component in 100% by mass is preferably 0.005 to 3% by mass, more preferably 0.007 to 1% by mass, and even more preferably 0.01 to 0.1% by mass.

[0257] When the polymer adhesive has a functional group (a), the metal-containing compound is preferably 1 to 100 mol% of the functional group (a), and more preferably 30 to 99 mol% of the metal element as an ion supply.

[0258] <Dispersion Medium>

[0259] The inorganic solid electrolyte composition of the present invention contains a dispersion medium that dissolves the binder to form a polymer and disperses the metal-containing compound.

[0260] As a dispersion medium, any organic compound that appears as a liquid in the environment can be used, such as various organic solvents. Specifically, examples include alcohols, ethers, amides, amines, ketones, aromatics, aliphatic compounds, nitriles, and esters.

[0261] The dispersion medium can be either a nonpolar (hydrophobic) or polar (hydrophilic) dispersion medium. From the viewpoint of achieving both the dissolved state of the polymer adhesive and the dispersed state of the metal-containing compound, a nonpolar dispersion medium is preferred. A nonpolar dispersion medium generally refers to a medium with low affinity for water; however, in this invention, a dispersion medium with a CLogP value of 1.5 to 6 is preferred. Examples of such media include ester compounds, ketone compounds, ether compounds, aromatic compounds, and aliphatic compounds.

[0262] Examples of alcohol compounds include, for example, methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, ethylene glycol, propylene glycol, glycerol, 1,6-hexanediol, cyclohexanediol, sorbitol, xylitol, 2-methyl-2,4-pentanediol, 1,3-butanediol, and 1,4-butanediol.

[0263] Examples of ether compounds include alkylene glycols (diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, etc.), alkylene glycol monoalkyl ethers (ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, diethylene glycol monobutyl ether, etc.), alkylene glycol dialkyl ethers (ethylene glycol dimethyl ether, etc.), dialkyl ethers (dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, etc.), and cyclic ethers (tetrahydrofuran, dioxanes (including 1,2-, 1,3- and 1,4- isomers, etc.)).

[0264] Examples of amide compounds include, for example, N,N-dimethylformamide, N-methyl-2-pyrrolidone, 2-pyrrolidone, 1,3-dimethyl-2-imidazolinone, ε-caprolactam, formamide, N-methylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropaneamide, hexamethylphosphoric triamide, etc.

[0265] Examples of amine compounds include triethylamine, diisopropylethylamine, and tri-n-butylamine.

[0266] Examples of ketone compounds include acetone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), cyclopentanone, cyclohexanone, cycloheptanone, dipropyl ketone, dibutyl ketone, diisopropyl ketone, diisobutyl ketone (DIBK), isobutylpropyl ketone, sec-butylpropyl ketone, pentylpropyl ketone, butylpropyl ketone, etc.

[0267] Examples of aromatic compounds include, for example, benzene, toluene, and xylene.

[0268] Examples of aliphatic compounds include hexane, heptane, octane, decane, cyclohexane, methylcyclohexane, ethylcyclohexane, cyclooctane, decahydronaphthalene, paraffin wax, gasoline, naphtha, kerosene, and light oil.

[0269] Examples of nitrile compounds include acetonitrile, propionitrile, and isobutyronitrile.

[0270] Examples of ester compounds include, for example, ethyl acetate, butyl acetate, propyl acetate, propyl butyrate, isopropyl butyrate, butyl butyrate, isobutyl butyrate, butyl valerate, ethyl isobutyrate, propyl isobutyrate, isopropyl isobutyrate, isobutyl isobutyrate, propyl neovalerate, isopropyl neovalerate, butyl neovalerate, isobutyl neovalerate, etc.

[0271] In this invention, ether compounds, ketone compounds, aromatic compounds, aliphatic compounds, and ester compounds are preferred, and ester compounds, ketone compounds, or ether compounds are more preferred.

[0272] There is no particular limitation on the number of carbon atoms in the compound constituting the dispersion medium, but it is preferably 2 to 30, more preferably 4 to 20, even more preferably 6 to 15, and especially preferably 7 to 12.

[0273] In the compound constituting the dispersion medium, the CLogP value is preferably 1 or more, more preferably 1.5 or more, even more preferably 2 or more, and particularly preferably 3 or more. There is no particular upper limit, but it is practically 10 or less, and preferably 6 or less.

[0274] In this invention, the CLogP value refers to the value obtained by calculating the common logarithm LogP of the partition coefficient P of 1-octanol and water. Any known method or software can be used to calculate the CLogP value; unless otherwise specified, PerkinElmer's ChemDraw is used to depict the structure and set the calculated value.

[0275] When there are two or more dispersion media, the CLogP value of the dispersion media is set as the sum of the products of the CLogP values ​​of each dispersion media and the mass fraction.

[0276] Examples of such dispersion media include toluene (CLogP = 2.5), xylene (CLogP = 3.12), hexane (CLogP = 3.9), heptane (Hep, CLogP = 4.4), octane (CLogP = 4.9), cyclohexane (CLogP = 3.4), cyclooctane (CLogP = 4.5), decahydronaphthalene (CLogP = 4.8), diisobutyl ketone (DIBK, CLogP = 3.0), dibutyl ether (DBE, CLogP = 2.57), butyl butyrate (CLogP = 2.8), tributylamine (CLogP = 4.8), methyl isobutyl ketone (MIBK, CLogP = 1.31), and ethylcyclohexane (ECH, CLogP = 3.4).

[0277] The boiling point of the dispersion medium at atmospheric pressure (1 atmosphere) is preferably 50°C or higher, more preferably 70°C or higher. The upper limit is preferably 250°C or lower, and even more preferably 220°C or lower.

[0278] The inorganic solid electrolyte composition of the present invention may contain at least one dispersion medium, or more than two.

[0279] In this invention, the content of the dispersion medium in the inorganic solid electrolyte composition is not particularly limited and can be appropriately set. For example, the inorganic solid electrolyte composition preferably contains 20-80% by mass, more preferably 30-70% by mass, and particularly preferably 40-60% by mass.

[0280] <Active Substances>

[0281] The inorganic solid electrolyte composition of the present invention may also contain an active material capable of intercalating or deintercalating ions of metals belonging to Group 1 or Group 2 of the periodic table. Examples of active materials, including positive electrode active materials and negative electrode active materials, will be described below.

[0282] In this invention, an inorganic solid electrolyte composition containing an active material (positive electrode active material or negative electrode active material) is sometimes referred to as an electrode composition (positive electrode composition or negative electrode composition).

[0283] (Positive electrode active material)

[0284] The positive electrode active material is preferably a positive electrode active material capable of reversibly inserting and deintercalating lithium ions. There are no particular restrictions as long as the material has the above-mentioned characteristics, and it can be a transition metal oxide of the decomposition battery or an element such as sulfur that can recombine with Li.

[0285] Among them, transition metal oxides are preferred as positive electrode active materials, and more preferably materials containing the transition metal element M. a A transition metal oxide (selected from one or more elements including Co, Ni, Fe, Mn, Cu, and V). Furthermore, element M may also be mixed into this transition metal oxide. b (Elements of Group 1(Ia) and Group 2(IIa) of the periodic table, excluding lithium, and elements such as Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, and B). As a mixing amount, it is preferable to be relative to the transition metal element M. a The amount (100 mol%) is 0-30 mol%. More preferably, it is Li / M a The mixtures were synthesized by mixing in a molar ratio of 0.3 to 2.2.

[0286] Specific examples of transition metal oxides include (MA) transition metal oxides with a layered rock salt structure, (MB) transition metal oxides with a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halophosphate compounds, and (ME) lithium-containing transition metal silicate compounds.

[0287] Specific examples of transition metal oxides (MA) with layered rock salt-type structures include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), and LiNi 0.85 Co 0.10 Al 0.05 O2 (lithium nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5Mn 0.5 O2 (lithium manganese nickel oxide).

[0288] Specific examples of transition metal oxides (MB) with spinel-type structures include LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8, and Li2NiMn3O8.

[0289] Examples of lithium-containing transition metal phosphates (MC) include olivine-type iron phosphates such as LiFePO4 and Li3Fe2(PO4)3, iron pyrophosphates such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic NASICON-type vanadium phosphates such as Li3V2(PO4)3 (lithium vanadium phosphate).

[0290] Examples of lithium-containing transition metal halophosphates (MD) include, for example, iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.

[0291] Examples of lithium-containing transition metal silicate compounds include, for example, Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4.

[0292] In this invention, (MA) is preferably a transition metal oxide having a layered rock salt structure, and more preferably LCO or NMC.

[0293] The shape of the positive electrode active material is not particularly limited, but particulate form is preferred. The particle size (volume average particle size) of the positive electrode active material is not particularly limited. For example, it can be set to 0.1–50 μm. The particle size of the positive electrode active material can be measured in the same manner as the particle size of the aforementioned inorganic solid electrolyte. To achieve the desired particle size, a conventional pulverizer or classifier is used. For example, a mortar, ball mill, sand mill, vibratory ball mill, satellite ball mill, planetary ball mill, and rotary airflow jet mill or sieve can be suitably used. During pulverization, wet pulverization with a dispersion medium such as water or methanol can also be appropriately performed. To achieve the desired particle size, classification is preferred. Classification is not particularly limited and can be performed using sieves, air classifiers, etc. Both dry and wet classification can be used.

[0294] Positive active materials obtained by sintering can also be used after being cleaned with water, acidic aqueous solutions, alkaline aqueous solutions, and organic solvents.

[0295] One type of positive electrode active material can be used alone, or two or more types can be used in combination.

[0296] When a positive electrode active material layer is formed, the per unit area (cm²) of the positive electrode active material layer... 2 There is no particular limitation on the mass (mg) (weight per unit area) of the positive electrode active material. It can be appropriately determined according to the designed battery capacity, for example, it can be set to 1 to 100 mg / cm³. 2 .

[0297] The content of the positive electrode active material in the inorganic solid electrolyte composition is not particularly limited, but it is preferably 10-97% by mass, more preferably 30-95% by mass, further preferably 40-93% by mass, and especially preferably 50-90% by mass in 100% by mass of the solid component.

[0298] (Negative electrode active material)

[0299] The preferred negative electrode active material is one capable of reversibly inserting and deintercalating lithium ions. There are no particular limitations on the material as long as it possesses the aforementioned properties; examples include carbonaceous materials, metal oxides, metal composite oxides, lithium monomers, lithium alloys, and negative electrode active materials capable of forming alloys with lithium. From a reliability perspective, carbonaceous materials, metal composite oxides, or lithium monomers are preferred.

[0300] Carbonaceous materials used as negative electrode active materials refer to materials that are essentially composed of carbon. Examples include carbonaceous materials produced by sintering petroleum asphalt, carbon black such as acetylene black (AB), graphite (natural graphite, vapor-grown graphite, and other artificial graphite), and various synthetic resins such as PAN (polyacrylonitrile) resins or furfuryl alcohol resins. Furthermore, examples include various types of carbon fibers such as PAN-based carbon fibers, cellulose-based carbon fibers, pitch-based carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol)-based carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers, as well as mesophase microspheres, graphite whiskers, and planar graphite.

[0301] These carbonaceous materials are classified into non-graphitized carbonaceous materials (also known as hard carbon) and graphite-based carbonaceous materials based on the degree of graphitization. Furthermore, the carbonaceous materials preferably possess the facet spacing or density and crystallite size described in Japanese Patent Application Publication Nos. 62-22066, 2-6856, and 3-45473. The carbonaceous material need not be a single material; mixtures of natural and artificial graphite as described in Japanese Patent Application Publication No. 5-90844, or coated graphite as described in Japanese Patent Application Publication No. 6-4516, etc., can also be used.

[0302] As a carbonaceous material, hard carbon or graphite is preferred, with graphite being more preferred.

[0303] As oxides of metals or half-metals suitable as negative electrode active materials, there are no particular limitations as long as they are oxides capable of absorbing and releasing lithium. Examples include oxides of metal elements (metal oxides), composite oxides of metal elements, or composite oxides of metal elements and half-metal elements (collectively referred to as metal composite oxides), and oxides of half-metal elements (half-metal oxides). Among these oxides, amorphous oxides are preferred, and further preferred are chalcogenides, products of the reaction between metal elements and elements of Group 16 of the periodic table. In this invention, a half-metal element refers to an element exhibiting intermediate properties between a metal element and a non-half-metal element, typically including six elements: boron, silicon, germanium, arsenic, antimony, and tellurium, and further including three elements: selenium, polonium, and astatine. Furthermore, amorphous refers to a material having a broad scattering band with vertices in the region of 20° to 40° at 2θ values ​​using CuKα X-ray diffraction, and may also have crystalline diffraction lines. The strongest intensity of the crystalline diffraction lines appearing in the region of 40° to 70° at a 2θ value is preferably 100 times or less than the intensity of the diffraction line at the apex of the broad scattering band appearing in the region of 20° to 40° at a 2θ value, more preferably 5 times or less, and especially preferably a non-crystalline diffraction line.

[0304] Among the compounds comprising the aforementioned amorphous oxides and chalcogenides, amorphous oxides of half-metallic elements or the aforementioned chalcogenides are more preferred, and (composite) oxides or chalcogenides comprising one or more elements selected from groups 13(IIIB) to 15(VB) of the periodic table (e.g., Al, Ga, Si, Sn, Ge, Pb, Sb, and Bi) are particularly preferred. Specific examples of preferred amorphous oxides and chalcogenides include, for example, Ga₂O₃, GeO, PbO, PbO₂, Pb₂O₃, Pb₂O₄, Pb₃O₄, Sb₂O₄, Sb₂O₈Bi₂O₃, Sb₂O₈Si₂O₃, Sb₂O₅, Bi₂O₃, Bi₂O₄, GeS, PbS, PbS₂, Sb₂S₃, or Sb₂S₅.

[0305] As a negative electrode active material that can be used with amorphous oxides centered on Sn, Si, and Ge, carbonaceous materials, lithium monomers, lithium alloys, and negative electrode active materials that can be alloyed with lithium are preferred examples.

[0306] From the viewpoint of high current density charge and discharge characteristics, oxides of metal or half-metal elements, especially metal (composite) oxides and the aforementioned chalcogenides, preferably contain at least one of titanium and lithium as constituent components. Examples of lithium-containing metal composite oxides (lithium composite metal oxides) include composite oxides of lithium oxide with the aforementioned metal (composite) oxides or chalcogenides; more specifically, Li₂SnO₂ can be cited.

[0307] Negative electrode active materials, such as metal oxides, are preferably those containing titanium (titanium oxide). Specifically, due to Li4Ti5O 12 Lithium titanate (LTO) exhibits minimal volume change during lithium ion adsorption and deintercalation, resulting in excellent high-speed charging and discharging characteristics. It is preferred in terms of both suppressing electrode degradation and improving the lifespan of lithium-ion secondary batteries.

[0308] There are no particular restrictions on the lithium alloy used as the negative electrode active material, as long as it is an alloy commonly used as the negative electrode active material in secondary batteries; for example, lithium-aluminum alloy can be cited.

[0309] There are no particular limitations on the negative electrode active material that can form an alloy with lithium, as long as it is a negative electrode active material commonly used in secondary batteries. Such active materials experience significant expansion and contraction during charging and discharging in all-solid-state secondary batteries, which accelerates the decline in cycle characteristics. However, the inorganic solid electrolyte composition of the present invention contains the aforementioned polymer binder and a metal-containing compound, thus suppressing the decline in cycle characteristics. Examples of such active materials include (negative electrode) active materials (alloys, etc.) containing silicon or tin, and various metals such as Al and In. Preferably, negative electrode active materials containing silicon (silicon-containing active materials) are preferred, as they enable higher battery capacity. More preferably, silicon-containing active materials have a silicon content of 50 mol% or more of all constituent elements.

[0310] Generally, negative electrodes containing these active materials (such as Si negative electrodes containing silicon-containing active materials and Sn negative electrodes containing tin-containing active materials) can absorb more Li ions compared to carbon negative electrodes (such as graphite and acetylene black). That is, the amount of Li ions retained per unit mass increases. Therefore, the battery capacity can be increased. As a result, it has the advantage of extending battery operating time.

[0311] Examples of silicon-containing active materials include silicon materials such as Si and SiOx (0 < x ≤ 1), as well as silicon-containing alloys (e.g., LaSi2, VSi2, La-Si, Gd-Si, Ni-Si) or structured active materials (e.g., LaSi2 / Si) containing elements such as titanium, vanadium, chromium, manganese, nickel, copper, and lanthanum. Additionally, active materials containing silicon elements such as SnSiO3 and SnSiS3, and tin elements, are also included. Furthermore, SiOx can be used as a negative electrode active material (a half-metal oxide) itself, and since Si is generated through the operation of an all-solid-state secondary battery, it can be used as a negative electrode active material (its precursor material) that can be alloyed with lithium.

[0312] Examples of anode active materials containing tin include those containing Sn, SnO, SnO2, SnS, SnS2, and the aforementioned silicon and tin elements. Furthermore, composite oxides with lithium oxide, such as Li2SnO2, can also be cited.

[0313] In this invention, the above-mentioned negative electrode active material can be used without particular limitations. However, from the viewpoint of battery capacity, it is preferable to use a negative electrode active material that can be alloyed with lithium. More preferably, it is the above-mentioned silicon material or silicon-containing alloy (an alloy containing silicon element). It is even more preferably to contain silicon (Si) or a silicon-containing alloy.

[0314] As a determination method, inductively coupled plasma (ICP) emission spectroscopy can be used. As a simple method, the chemical formula of the compound obtained by the above-mentioned firing method can be calculated from the mass difference of the powder before and after firing.

[0315] The shape of the negative electrode active material is not particularly limited, but it is preferably particulate. The volume average particle size of the negative electrode active material is not particularly limited, but is preferably 0.1–60 μm. The volume average particle size of the negative electrode active material can be measured in the same manner as the average particle size of the inorganic solid electrolyte described above. To achieve the specified particle size, a conventional pulverizer or classifier is used, similar to that used for the positive electrode active material.

[0316] The above-mentioned negative electrode active material can be used alone or in combination of two or more.

[0317] When a negative electrode active material layer is formed, the per unit area (cm²) of the negative electrode active material layer... 2 There is no particular limitation on the mass (mg) (weight per unit area) of the negative electrode active material. It can be appropriately determined according to the designed battery capacity, for example, it can be set to 1 to 100 mg / cm³. 2 .

[0318] The content of the negative electrode active material in the inorganic solid electrolyte composition is not particularly limited, but is preferably 10-90% by mass, more preferably 20-85% by mass, more preferably 30-80% by mass, and even more preferably 40-75% by mass in 100% by mass of solid components.

[0319] In this invention, when the negative electrode active material layer is formed by charging a secondary battery, ions of metals belonging to Group I or Group II of the periodic table generated within the all-solid-state secondary battery can be used instead of the aforementioned negative electrode active material. By bonding these ions with electrons and depositing them as metal, the negative electrode active material layer can be formed.

[0320] (Coating of active substances)

[0321] The surfaces of both the positive and negative electrode active materials can be coated with different metal oxides. Examples of surface coating agents include metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si, or Li. Specifically, examples include spinel titanate, tantalum oxides, niobium oxides, and lithium niobate compounds; for instance, Li₄Ti₅O₅ can be used. 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3, etc.

[0322] Furthermore, the electrode surface containing positive or negative active materials can be surface-treated with sulfur or phosphorus.

[0323] Furthermore, the particle surface of the positive or negative active material can be surface-treated by photochemical rays or active gas (plasma, etc.) before and after the aforementioned surface coating.

[0324] <Conductive additives>

[0325] The inorganic solid electrolyte composition of the present invention preferably contains a conductive additive, for example, a silicon-containing active material as a negative electrode active material is used in combination with the conductive additive.

[0326] There are no particular restrictions on the conductive additives used; any conductive additives known to be used as conductive additives can be used. For example, they can be graphite materials such as natural graphite and artificial graphite, carbon black such as acetylene black, Ketjen black, and furnace black, amorphous carbon such as needle coke, carbon fiber materials such as vapor-grown carbon fibers or carbon nanotubes, carbonaceous materials such as graphene or fullerene, metal powders such as copper and nickel, metal fibers, or conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives.

[0327] In this invention, when active materials and conductive additives are used in combination, the conductive additives that do not produce the insertion and extraction of metal ions (preferably Li ions) belonging to Group I or Group II of the periodic table during battery charging and discharging, and do not function as active materials, are classified as conductive additives. Therefore, among conductive additives, those that can function as active materials in the active material layer during battery charging and discharging are classified as active materials rather than conductive additives. Whether or not they function as active materials during battery charging and discharging is determined by their combination with active materials, rather than by a general rule.

[0328] The conductive additive may contain one type or two or more types.

[0329] There are no particular restrictions on the shape of the conductive additive, but it is preferably in particulate form.

[0330] When the inorganic solid electrolyte composition of the present invention contains a conductive additive, the content of the conductive additive in the inorganic solid electrolyte composition is preferably 0 to 10% by mass of 100% by mass of the solid component.

[0331] <Lithium Salts>

[0332] The inorganic solid electrolyte composition of the present invention preferably also contains a lithium salt (supporting electrolyte).

[0333] As a lithium salt, the lithium salt commonly used in this product is preferred, and there are no particular limitations. For example, the lithium salt described in paragraphs 0082 to 0085 of Japanese Patent Application Publication No. 2015-088486 is preferred.

[0334] When the inorganic solid electrolyte composition of the present invention contains a lithium salt, the content of the lithium salt relative to 100 parts by weight of the solid electrolyte is preferably 0.1 parts by weight or more, more preferably 5 parts by weight or more. As an upper limit, it is preferably 50 parts by weight or less, more preferably 20 parts by weight or less.

[0335] <Dispersant>

[0336] In the inorganic solid electrolyte composition of the present invention, the aforementioned polymer binder also functions as a dispersant; therefore, it may or may not contain a dispersant other than the polymer binder. As a dispersant, a dispersant commonly used in all-solid-state secondary batteries can be suitably selected. Typically, compounds suitable for particle adsorption, steric hindrance, and / or electrostatic repulsion are used.

[0337] <Other Additives>

[0338] The inorganic solid electrolyte composition of the present invention can appropriately contain ionic liquids, thickeners, crosslinking agents (substances that undergo crosslinking reactions via free radical polymerization, condensation polymerization, or ring-opening polymerization, etc.), polymerization initiators (substances that generate acids or free radicals through heat or light, etc.), defoamers, homogenizers, dehydrating agents, antioxidants, etc., as other components besides those mentioned above. The ionic liquid is a liquid contained to further improve ionic conductivity, and known liquids can be used without particular limitation. Furthermore, polymers other than the polymers forming the aforementioned polymer binder can contain commonly used adhesives, etc.

[0339] (Preparation of inorganic solid electrolyte compositions)

[0340] The inorganic solid electrolyte composition of the present invention can be prepared by mixing, for example, an inorganic solid electrolyte, a polymer binder, a metal-containing compound, a dispersion medium, a conductive additive, a suitable lithium salt, and any other components in various commonly used mixers. Thus, it is preferably prepared as a slurry, a mixture in which the polymer binder is dissolved relative to the dispersion medium and the metal-containing compound is insoluble and exists in a solid state. In the case of an electrode composition, an active material is further mixed. When preparing the composition, the polymer binder, the metal-containing compound, and the dispersion medium can be suitably selected to represent a combination of the aforementioned dissolved and dispersed states relative to the dispersion medium.

[0341] There are no particular restrictions on the mixing method; mixing can be done all at once or sequentially. There are also no particular restrictions on the mixing environment; examples include mixing under dry air or under an inert gas atmosphere.

[0342] When the inorganic solid electrolyte composition of the present invention meets the above-mentioned content, the polymer binder and the metal-containing compound do not readily react with each other at room temperature. For example, even if the above-mentioned salt exchange reaction occurs, the proportion is small enough to maintain the dispersion stability of the composition. In the present invention, in order to generate an interaction sufficient to cure the polymer binder, the film-forming conditions described later are preferably applied.

[0343] <Properties or physical properties of compositions containing inorganic solid electrolytes>

[0344] The inorganic solid electrolyte composition of the present invention is preferably a non-aqueous composition. In the present invention, the non-aqueous composition, in addition to being free of water, also contains a water content (also referred to as moisture content) preferably of 500 ppm or less. In the non-aqueous composition, the water content is more preferably 200 ppm or less, further preferably 100 ppm or less, and particularly preferably 50 ppm or less. If the inorganic solid electrolyte composition is a non-aqueous composition, the degradation of the inorganic solid electrolyte can be suppressed. The water content refers to the amount of water contained in the inorganic solid electrolyte composition (mass ratio of the inorganic solid electrolyte composition), specifically, it is defined as the value obtained by filtration using a 0.02 μm membrane filter and determination using Karl Fischer titration.

[0345] In the inorganic solid electrolyte composition of the present invention, the viscosity (initial viscosity) after preparation is not particularly limited, but considering factors such as coatability, the viscosity under the following measurement conditions is preferably 1000 to 4000 cP, more preferably 300 to 4000 cP, and even more preferably 500 to 2500 cP. The inorganic solid electrolyte composition of the present invention exhibits excellent dispersion characteristics as described above, and therefore the above-mentioned initial viscosity can be maintained over time.

[0346] -Determination Conditions-

[0347] Temperature: 23℃

[0348] Shear rate: 10 / s

[0349] Measurement equipment: TV-35 viscometer (manufactured by Toki Sangyo Co., Ltd.)

[0350] Measurement method: Add 1.1 ml of the composition to the sample cup, place the sample cup on the viscometer body equipped with a standard conical rotor (1°34'×R24), set the measurement range to "U", rotate at the above shear rate and read the value after 1 minute.

[0351] The inorganic solid electrolyte composition of the present invention preferably exhibits a lower solubility in the dispersion medium of the polymer binder after heating to 80°C or above compared to the solubility of the polymer binder before heating. By reducing the solubility of the polymer binder through heating, it is possible to solidify the polymer binder as particles from the dispersion medium during film formation (drying) of the inorganic solid electrolyte composition, maintaining excellent dispersion characteristics while suppressing an increase in resistance, and achieving excellent cycling characteristics.

[0352] The aforementioned characteristics of the inorganic solid electrolyte composition (the decrease in solubility due to heating) can be evaluated and confirmed as long as it is an inorganic solid electrolyte composition of the present invention. However, as shown in Example 2 below, if the composition in which the content of the polymer binder is set to 10% by mass and the content of the composition containing the metal element compound is set to 0.5% by mass, the evaluation and confirmation can be more clearly achieved.

[0353] If the heating temperature is above 80°C, the above characteristics can be evaluated and confirmed more clearly; for example, it can be set to 80–120°C. In addition, the heating temperature and conditions other than content can be appropriately determined, such as the heating time being set to 10 minutes or more.

[0354] In the inorganic solid electrolyte composition of the present invention, when the total concentration of the polymer binder and the metal-containing compound in the inorganic solid electrolyte composition is concentrated to 30% by mass or more, it is preferable that the solubility of the concentrated polymer binder in the dispersion medium becomes less than the solubility of the polymer binder in the dispersion medium before concentration. If the solubility of the polymer binder is reduced by concentration, the polymer binder can be solidified as particles from the dispersion medium during film formation (drying) of the inorganic solid electrolyte composition, maintaining excellent dispersion characteristics while suppressing an increase in resistance, and achieving excellent cycling characteristics.

[0355] The aforementioned characteristics of the inorganic solid electrolyte composition (the decrease in solubility due to concentration) can be evaluated and confirmed as long as it is an inorganic solid electrolyte composition of the present invention. However, as shown in Example 2 below, if the composition in which the content of the polymer binder is set to 10% by mass and the content of the composition containing the metal element compound is set to 0.5% by mass, the evaluation and confirmation can be more clearly achieved.

[0356] If the total concentration of the concentrate is 30% by mass or higher, the aforementioned characteristics can be evaluated and confirmed more clearly; for example, it can be set to 50% by mass or higher. Furthermore, the heating temperature during concentration can be appropriately set, preferably above 80°C, but preferably below 80°C, to minimize the risk of decreased solubility due to heating; for example, it can be set to 30–60°C. Additionally, conditions other than the total content and heating temperature can be appropriately determined.

[0357] When the inorganic solid electrolyte composition of the present invention forms a constituent layer by film formation, it is preferable that the solubility of the polymer binder present in the constituent layer in the dispersion medium previously contained in the inorganic solid electrolyte composition becomes less than the solubility of the polymer binder contained in the inorganic solid electrolyte composition in the dispersion medium. By reducing the solubility of the polymer binder through the film formation process, the polymer binder can be cured from the dispersion medium to form polymer binder particles in the constituent layer, thereby suppressing the increase in resistance and achieving excellent cycling characteristics.

[0358] The aforementioned characteristics of the inorganic solid electrolyte composition (the decrease in solubility caused by film formation) can be evaluated and confirmed as long as it is an inorganic solid electrolyte composition of the present invention. If the composition in which the content of the polymer binder is set to 10% by mass and the content of the composition containing the metal element compound is set to 0.5% by mass, the evaluation and confirmation can be made more clearly.

[0359] There are no particular restrictions on the film-forming conditions, and the drying conditions described later can be appropriately selected.

[0360] In the aforementioned solubility reduction characteristics caused by heating, concentration, or film formation, the solubility of the polymer binder only needs to be reduced to a level sufficient to allow it to solidify and precipitate from the dispersion medium; preferably, the solubility difference is 20% by mass or more. This reduction in solubility is believed to be due to the interaction between the dissolved polymer binder and the metal-containing compound.

[0361] [Sheets for all-solid-state rechargeable batteries]

[0362] The sheet material for all-solid-state secondary batteries of the present invention is a sheet-shaped molded body capable of forming the constituent layers of an all-solid-state secondary battery, and includes various forms depending on its application. For example, sheets preferably used for solid electrolyte layers (also called solid electrolyte sheets for all-solid-state secondary batteries) and sheets preferably used for electrodes or laminates of electrodes and solid electrolyte layers (electrode sheets for all-solid-state secondary batteries) are examples. In the present invention, these various sheets are collectively referred to as sheets for all-solid-state secondary batteries.

[0363] The solid electrolyte sheet for all-solid-state secondary batteries of the present invention can be any sheet having a solid electrolyte layer. It can be a sheet with the solid electrolyte layer formed on a substrate, or it can be a sheet without a substrate, formed solely by the solid electrolyte layer. In addition to the solid electrolyte layer, the solid electrolyte sheet for all-solid-state secondary batteries may also have other layers. Examples of other layers include, for instance, a protective layer (release sheet), a current collector, and a coating.

[0364] As an example of the solid electrolyte sheet for an all-solid-state secondary battery according to the present invention, a sheet having, in sequence, a layer composed of the inorganic solid electrolyte composition of the present invention, a conventional solid electrolyte layer, and a protective layer on a substrate is exemplified. The layer thickness of each layer constituting the solid electrolyte sheet for an all-solid-state secondary battery is the same as the layer thickness described later in the description of all-solid-state secondary batteries.

[0365] The solid electrolyte layer of the solid electrolyte sheet for all-solid-state secondary batteries is formed by the inorganic solid electrolyte composition of the present invention.

[0366] In the film-forming process of the inorganic solid electrolyte composition of the present invention, the polymer binder in a dissolved state interacts with the metal-containing compound, maintaining adsorption to solid particles while solidifying into particles. Therefore, the solid electrolyte layer composed of this inorganic solid electrolyte composition contains particles (particle-shaped solidified material) derived from the polymer binder. The average particle size of the particles derived from the polymer binder in the solid electrolyte layer is not particularly limited and can be set to 5–1600 nm. From the viewpoint of improving dispersion characteristics and battery characteristics, 8–1200 nm is preferred, more preferably 10–800 nm, and even more preferably 30–600 nm. The average particle size is a value measured by the method described in the examples described later.

[0367] The average particle size can be adjusted, for example, by the characteristics of the polymer binder (type, composition, molecular weight, etc.), the type of metal-containing compound (anionic or metal element type), the content of the polymer binder and the metal-containing compound, the type of dispersion medium, and the film-forming conditions.

[0368] There are no particular restrictions on the state of the metal-containing compounds in the solid electrolyte layer. The metal-containing compounds that supply the metal elements can exist as anions or as conjugate acids obtained by bonding anions and hydrogen atoms through salt exchange reactions.

[0369] The polymer binder (particulate cured material) present in the solid electrolyte layer is produced by curing from a dissolved state through the aforementioned interactions. Therefore, the solubility of the polymer binder present in the solid electrolyte layer relative to the dispersion medium contained in the inorganic solid electrolyte composition becomes less than the solubility of the polymer binder contained in the inorganic solid electrolyte composition (before the interaction) relative to the aforementioned dispersion medium. The decrease in the solubility of the polymer binder before and after interaction with the metal-containing compound can be confirmed by the measurement methods described in the examples below.

[0370] The content of each component in the solid electrolyte layer is not particularly limited, and the preferred meaning is the same as the meaning of the content of each component in the solid component of the inorganic solid electrolyte composition of the present invention.

[0371] As for the substrate, there are no particular limitations as long as it is a substrate capable of supporting the solid electrolyte layer. Examples include the materials described in the current collector section, organic materials, inorganic materials, and sheet-like materials. Examples of organic materials include various polymers, specifically polyethylene terephthalate, polypropylene, polyethylene, and cellulose. Examples of inorganic materials include, for example, glass and ceramics.

[0372] The electrode sheet for all-solid-state secondary batteries of the present invention (also simply referred to as "electrode sheet") can be any electrode sheet having an active material layer. It can be a sheet in which the active material layer is formed on a substrate (current collector), or it can be a sheet formed by the active material layer without a substrate. The electrode sheet is usually a sheet having a current collector and an active material layer, but it also includes forms having a current collector, an active material layer and a solid electrolyte layer in sequence, as well as forms having a current collector, an active material layer, a solid electrolyte layer and an active material layer in sequence.

[0373] At least one of the solid electrolyte layer and active material layer of the electrode sheet is formed by the inorganic solid electrolyte composition of the present invention. In the solid electrolyte layer and active material layer formed by the inorganic solid electrolyte composition of the present invention, the polymer binder and the metal-containing compound are present in the same state as in the solid electrolyte layer of the solid electrolyte sheet for the all-solid-state secondary battery described above. Furthermore, the content of each component in the solid electrolyte layer or active material layer is not particularly limited, and the preferred meaning is the same as the meaning of the content of each component in the solid components of the inorganic solid electrolyte composition (electrode composition) of the present invention. The layer thickness of each layer constituting the electrode sheet of the present invention is the same as the layer thickness described later in the all-solid-state secondary battery section. The electrode sheet of the present invention may have the other layers described above.

[0374] In addition, when the solid electrolyte layer or active material layer is not formed by the inorganic solid electrolyte composition of the present invention, it is formed by a conventional constituent layer forming material.

[0375] In the all-solid-state secondary battery sheet of the present invention, at least one of the solid electrolyte layer and the active material layer is formed from the inorganic solid electrolyte composition of the present invention, resulting in a structural layer with a flat surface and low resistance. Therefore, the all-solid-state secondary battery sheet of the present invention, when used as a structural layer of an all-solid-state secondary battery, enables the realization of low resistance (high conductivity) and excellent cycle characteristics in the all-solid-state secondary battery. In particular, in the all-solid-state secondary battery electrode sheet and the all-solid-state secondary battery in which the active material layer is formed from the inorganic solid electrolyte composition of the present invention, the active material layer and the current collector exhibit strong adhesion, further improving cycle characteristics. Therefore, the all-solid-state secondary battery sheet of the present invention is suitable as a sheet capable of forming a structural layer of an all-solid-state secondary battery.

[0376] [Manufacturing Method of Sheets for All-Solid-State Secondary Batteries]

[0377] The manufacturing method of the all-solid-state secondary battery sheet of the present invention is not particularly limited, and it can be manufactured by forming the above-mentioned layers using the inorganic solid electrolyte composition of the present invention. Preferably, a method is described where a film is formed (coated and dried) on a substrate or current collector (which may be via another layer) to form a layer (coated and dried layer) composed of the inorganic solid electrolyte composition. This allows the production of an all-solid-state secondary battery sheet having a substrate or current collector and a coated and dried layer. Here, the coated and dried layer refers to a layer formed by coating the inorganic solid electrolyte composition of the present invention and drying the dispersion medium (i.e., a layer formed using the inorganic solid electrolyte composition of the present invention, and with the dispersion medium removed from the inorganic solid electrolyte composition of the present invention). The dispersion medium may remain in the active material layer and the coated and dried layer as long as it does not impair the effects of the present invention; the residual amount can be, for example, 3% by mass or less in each layer. As described above, the coated and dried layer contains particles derived from the polymer binder.

[0378] In the manufacturing method of the all-solid-state secondary battery sheet of the present invention, each step such as coating and drying will be described in the following manufacturing method of the all-solid-state secondary battery.

[0379] In the preferred method described above, when the inorganic solid electrolyte composition of the present invention is filmed on a current collector to produce a sheet for an all-solid-state secondary battery, the adhesion between the current collector and the active material layer can be made stronger.

[0380] In the method for manufacturing the sheet material for all-solid-state secondary batteries of the present invention, pressure can also be applied to the coated and dried layer. The pressure conditions, etc., will be explained in the manufacturing method for all-solid-state secondary batteries described later.

[0381] The obtained coated and dried layer becomes a solid electrolyte layer or an active material layer through appropriate pressure treatment.

[0382] Furthermore, in the manufacturing method of the all-solid-state secondary battery sheet of the present invention, it is also possible to peel off the substrate, protective layer (especially the sheet), etc.

[0383] [All-solid-state rechargeable battery]

[0384] The all-solid-state secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The positive electrode active material layer is preferably formed on a positive electrode current collector and constitutes the positive electrode. The negative electrode active material layer is preferably formed on a negative electrode current collector and constitutes the negative electrode.

[0385] At least one of the negative electrode active material layer, the positive electrode active material layer, and the solid electrolyte layer is formed by the inorganic solid electrolyte composition of the present invention, preferably the solid electrolyte layer or at least one of the negative electrode active material layer and the positive electrode active material layer is formed by the inorganic solid electrolyte composition of the present invention.

[0386] It is also a preferred embodiment that all layers are formed from the inorganic solid electrolyte composition of the present invention. In the present invention, the formation of the constituent layers of an all-solid-state secondary battery from the inorganic solid electrolyte composition of the present invention refers to a method in which the constituent layers are formed from the sheet material for all-solid-state secondary batteries of the present invention (wherein, the sheet material obtained by removing layers other than those formed from the inorganic solid electrolyte composition of the present invention). Regarding the types and amounts of the components contained, the active material layer or solid electrolyte layer formed from the inorganic solid electrolyte composition of the present invention is preferably the same as that in the solid components of the inorganic solid electrolyte composition of the present invention. Furthermore, when the active material layer or solid electrolyte layer is not formed from the inorganic solid electrolyte composition of the present invention, known materials can be used.

[0387] There are no particular limitations on the thickness of the negative electrode active material layer, the solid electrolyte layer, and the positive electrode active material layer. Considering the size of a typical all-solid-state secondary battery, the thickness of each layer is preferably 10 to 1,000 μm, more preferably 20 μm or more and less than 500 μm. In the all-solid-state secondary battery of the present invention, the thickness of at least one of the positive electrode active material layer and the negative electrode active material layer is further preferably 50 μm or more and less than 500 μm.

[0388] The positive electrode active material layer and the negative electrode active material layer can each have a current collector on the side opposite to the solid electrolyte layer.

[0389] <Frame>

[0390] The all-solid-state secondary battery of the present invention can be used as an all-solid-state secondary battery in the above-described structural state depending on the application, but in order to make it into a dry cell form, it is preferable to further enclose it in a suitable casing. The casing can be a metallic casing or a resin (plastic) casing. When using a metallic casing, for example, a casing made of aluminum alloy or stainless steel can be cited. Preferably, the metallic casing is divided into a positive electrode side casing and a negative electrode side casing, which are electrically connected to the positive electrode current collector and the negative electrode current collector, respectively. Preferably, the positive electrode side casing and the negative electrode side casing are joined together as one piece with a short-circuit prevention gasket.

[0391] The following is for reference. Figure 1 The preferred embodiments of the present invention will be described, but the present invention is not limited thereto.

[0392] Figure 1 This is a schematic cross-sectional view illustrating a preferred embodiment of the all-solid-state secondary battery (lithium-ion secondary battery) of the present invention. Viewed from the negative electrode side, the all-solid-state secondary battery 10 of this embodiment sequentially comprises a negative electrode current collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode current collector 5. Each layer is in contact with the others and has an adjacent structure. By employing such a structure, electrons (electrons) are supplied to the negative electrode side during charging. - ), and accumulate lithium ions (Li) here. + On the other hand, during discharge, lithium ions (Li) accumulated at the negative electrode... + The electrons return to the positive side and supply electrons to the working part 6. In the illustrated example, a light bulb is used as a model in the working part 6, and the bulb is lit by discharging.

[0393] In having Figure 1 When the layered solid-state secondary battery shown is placed in a 2032-type button cell, it is sometimes referred to as a laminate for solid-state secondary batteries. A battery made by placing the laminate for solid-state secondary batteries in a 2032-type button cell is called a solid-state secondary battery.

[0394] (Positive electrode active material layer, solid electrolyte layer, negative electrode active material layer)

[0395] In the all-solid-state secondary battery 10, the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer are all formed from the inorganic solid electrolyte composition of the present invention. This all-solid-state secondary battery 10 exhibits excellent battery performance. The polymer binder and metal-containing compound in the positive electrode active material layer 4, the solid electrolyte layer 3, and the negative electrode active material layer 2 exist in the same state as in the solid electrolyte layer of the solid electrolyte sheet for the all-solid-state secondary battery described above. The inorganic solid electrolyte and polymer binder contained in the positive electrode active material layer 4, the solid electrolyte layer 3, and the negative electrode active material layer 2 can be of the same type or different types.

[0396] In this invention, either or both of the positive electrode active material layer and the negative electrode active material layer are simply referred to as the active material layer or the electrode active material layer. Furthermore, either or both of the positive electrode active material and the negative electrode active material are collectively referred to as the active material or the electrode active material.

[0397] In this invention, when the constituent layer is formed by the inorganic solid electrolyte composition of this invention, an all-solid-state secondary battery with low resistance and exhibiting excellent cycle characteristics can be realized.

[0398] In the all-solid-state secondary battery 10, the negative electrode active material layer can be a lithium metal layer. Examples of lithium metal layers include layers formed by stacking or molding lithium metal powder, lithium foil, and lithium vapor-deposited films. The thickness of the lithium metal layer is independent of the aforementioned thickness of the negative electrode active material layer, and for example, can be set to 1 to 500 μm.

[0399] The positive current collector 5 and the negative current collector 1 are preferably electron conductors.

[0400] In this invention, either the positive current collector or the negative current collector, or both together, are sometimes referred to simply as a current collector.

[0401] In addition to aluminum, aluminum alloys, stainless steel, nickel, and titanium, materials in which carbon, nickel, titanium, or silver (materials forming thin films) are treated on the surface of aluminum or stainless steel are preferred as the material forming the positive current collector. Among these, aluminum and aluminum alloys are more preferred.

[0402] In addition to aluminum, copper, copper alloys, stainless steel, nickel, and titanium, materials that have been treated with carbon, nickel, titanium, or silver on the surface of aluminum, copper, copper alloys, or stainless steel are preferred as materials for forming the negative current collector. More preferably, aluminum, copper, copper alloys, and stainless steel are preferred.

[0403] Current collectors are typically in the form of a membrane, but can also be made of mesh, perforated material, lath, porous material, foam, or fiber assembly.

[0404] There is no particular limitation on the thickness of the current collector, but it is preferably 1 to 500 μm. Furthermore, it is also preferable to have irregularities on the surface of the current collector through surface treatment.

[0405] In the aforementioned all-solid-state secondary battery 10, the positive electrode active material layer can also be a layer formed by a known constituent layer forming material.

[0406] In this invention, functional layers, components, etc., can be appropriately inserted or disposed between or on the outer sides of the negative electrode current collector, negative electrode active material layer, solid electrolyte layer, positive electrode active material layer, and positive electrode current collector. Furthermore, each layer can be configured as a single layer or as multiple layers.

[0407] [Manufacturing of all-solid-state rechargeable batteries]

[0408] All-solid-state secondary batteries can be manufactured using conventional methods. Specifically, all-solid-state secondary batteries can be manufactured by forming the aforementioned layers using the inorganic solid electrolyte composition of the present invention. This will be described in detail below.

[0409] The all-solid-state secondary battery of the present invention can be manufactured by performing a method comprising (via) appropriately coating the inorganic solid electrolyte composition of the present invention onto a substrate (e.g., a metal foil serving as a current collector) and drying it to form a coating film (film forming).

[0410] For example, a positive electrode active material layer is formed by forming a film of an inorganic solid electrolyte composition containing a positive electrode active material (positive electrode composition) on a metal foil serving as the positive electrode current collector, thereby producing a positive electrode sheet for an all-solid-state secondary battery. Next, an inorganic solid electrolyte composition for forming a solid electrolyte layer is formed by forming a film on this positive electrode active material layer. Furthermore, a negative electrode active material layer is formed by forming a film of an inorganic solid electrolyte composition containing a negative electrode active material (negative electrode composition) on the solid electrolyte layer. By overlapping a negative electrode current collector (metal foil) on the negative electrode active material layer, an all-solid-state secondary battery with a structure in which the solid electrolyte layer is sandwiched between the positive and negative electrode active material layers can be obtained. It can also be encapsulated in a casing to form a desired all-solid-state secondary battery.

[0411] Furthermore, in contrast to the methods for forming each layer, it is also possible to manufacture an all-solid-state secondary battery by forming a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer on the negative electrode current collector and then overlapping the positive electrode current collector.

[0412] As another method, the following approach can be used: The positive electrode sheet for an all-solid-state secondary battery is manufactured as described above. Furthermore, an inorganic solid electrolyte composition containing negative electrode active material is formed on a metal foil serving as the negative electrode current collector to create a negative electrode active material layer, thus manufacturing the negative electrode sheet for an all-solid-state secondary battery. Next, a solid electrolyte layer is formed on the active material layer of any one of these sheets, as described above. Then, the positive electrode sheet for an all-solid-state secondary battery and another negative electrode sheet for an all-solid-state secondary battery are stacked on the solid electrolyte layer in such a way that the solid electrolyte layer and the active material layer are in contact. In this way, an all-solid-state secondary battery can be manufactured.

[0413] Furthermore, as another method, the following can be cited: That is, to manufacture the positive electrode sheet and the negative electrode sheet for an all-solid-state secondary battery as described above. In addition, a solid electrolyte sheet for an all-solid-state secondary battery, consisting of a solid electrolyte layer, can be manufactured by forming a film containing an inorganic solid electrolyte composition on a substrate. Moreover, the solid electrolyte layer, which has been peeled off from the substrate, is stacked in a manner where the positive electrode sheet and the negative electrode sheet for an all-solid-state secondary battery are sandwiched between them. In this way, an all-solid-state secondary battery can be manufactured.

[0414] Solid electrolyte layers, for example, are formed by pressurizing an inorganic solid electrolyte composition onto a substrate or active material layer under pressure conditions described later.

[0415] In the above manufacturing method, the inorganic solid electrolyte composition of the present invention can be used for any one of the positive electrode composition, the inorganic solid electrolyte composition, and the negative electrode composition. It is preferred to use the inorganic solid electrolyte composition of the present invention for the inorganic solid electrolyte composition, but the inorganic solid electrolyte composition of the present invention can also be used for any composition.

[0416] <Formation of each layer (film formation)>

[0417] The film formation (coating and drying) of the inorganic solid electrolyte composition of the present invention is performed simultaneously with curing the polymer binder into particles. There are no particular limitations on the method of curing into particles; for example, methods such as reducing the solubility of the polymer binder contained in the inorganic solid electrolyte composition in the dispersion medium while forming a film, or heating the inorganic solid electrolyte composition to 80°C or higher to form a film, are also possible.

[0418] There are no particular limitations on the coating method for the inorganic solid electrolyte composition, and appropriate methods can be selected. Examples include coating (preferably wet coating), spraying, spin coating, dip coating, slot coating, strip coating, and bar coating.

[0419] The coated inorganic solid electrolyte composition is subjected to a drying treatment (heat treatment). During the drying treatment, the polymer binder, dissolved in the coated inorganic solid electrolyte composition, maintains its adsorption to the solid particles while curing into particles, thereby suppressing the increase in interfacial resistance and bonding the solid particles together. Through the curing of this polymer binder, combined with the excellent dispersion characteristics of the inorganic solid electrolyte composition, it is possible to bond the solid particles while suppressing fluctuations in the contact state and the increase in interfacial resistance, and to form a coated dried layer with a flat surface.

[0420] It is believed that during the drying process, when the inorganic solid electrolyte composition of the present invention is heated, the dispersion medium evaporates as the temperature rises, the concentration of the solid components gradually increases (concentrates), promoting the expression of the interaction between the polymer binder and the metal-containing compound (e.g., salt exchange reaction), and the solubility of the polymer binder in the dispersion medium gradually decreases. Thus, the polymer binder solidifies into particles.

[0421] The drying process can be carried out after coating the inorganic solid electrolyte composition separately, or after multi-layer coating.

[0422] There are no particular limitations on drying conditions as long as they exhibit the aforementioned interactions, and conditions that reduce the solubility of the polymer binder in the dispersion medium can be preferred. Examples include drying methods and drying temperatures.

[0423] There are no particular limitations on the drying method; conventional drying methods such as air drying, air drying, and heat drying under atmospheric or reduced pressure can be used. The inorganic solid electrolyte composition of the present invention exhibits excellent dispersion characteristics. Furthermore, in the above-mentioned drying process, the total concentration of the polymer binder and the metal-containing compound in the coated inorganic solid electrolyte composition necessarily reaches 30% by mass or more, and the solubility of the polymer binder decreases. Therefore, air drying can be used as the drying method for the inorganic solid electrolyte composition of the present invention. However, in the present invention, in order to quickly manifest the above-mentioned interaction, a drying method or drying condition that actively removes the dispersion medium is preferred, and heat drying is more preferred. The conditions in each drying method can be appropriately determined by considering the amount of decrease in the solubility of the polymer binder and, more preferably, the amount of volatilization of the dispersion medium (increase in the concentration of the polymer binder and the metal-containing compound). In the present invention, it is preferable to set the drying temperature of the coated inorganic solid electrolyte composition. The drying temperature is not unique depending on the drying method; for example, it is preferably 30°C or higher, more preferably 60°C or higher, and even more preferably 80°C or higher. There is no particular upper limit. For example, from the viewpoint of preventing damage to the components of the all-solid-state secondary battery, it is preferable to be below 300°C, more preferably below 250°C, and even more preferably below 200°C.

[0424] All-solid-state secondary batteries with such a constituent layer exhibit excellent overall performance and can achieve good adhesion and good ion conductivity even without pressure.

[0425] After coating with an inorganic solid electrolyte composition, the layers are stacked to form a composite, or after fabricating an all-solid-state secondary battery, each layer or the all-solid-state secondary battery is pressurized. Furthermore, pressurization is preferably performed while the layers are stacked. Examples of pressurization methods include hydraulic cylinder presses. The pressure applied is not particularly limited, but is generally preferred to be in the range of 5 to 1500 MPa.

[0426] Furthermore, the coated inorganic solid electrolyte composition can be heated simultaneously with pressurization. There are no particular limitations on the heating temperature, which is generally in the range of 30 to 300°C. Stamping can also be performed at temperatures higher than the glass transition temperature of the inorganic solid electrolyte. Additionally, stamping can also be performed at temperatures higher than the glass transition temperature of the polymer contained in the polymer binder. However, the temperature is generally no higher than the melting point of the polymer.

[0427] Pressurization can be performed either with the solvent or dispersion medium pre-dried or with residual solvent or dispersion medium remaining.

[0428] Alternatively, the various compositions can be coated simultaneously, or the coating, drying, and stamping can be performed simultaneously and / or sequentially. They can be laminated by transfer printing after being coated onto their respective substrates.

[0429] There are no particular restrictions on the pressurized environment; it can be any environment, such as atmospheric pressure, dry air (dew point below -20°C), or inert gases (e.g., argon, helium, nitrogen).

[0430] The stamping time can be either a short period of time (e.g., within a few hours) to apply high pressure, or a long period of time (more than one day) to apply medium pressure. In the case of solid-state secondary batteries, except for sheets for all-solid-state secondary batteries, medium pressure can be continuously applied using the constraint tools of all-solid-state secondary batteries (such as screw tightening pressure).

[0431] Compared to the pressure-bearing parts such as the surface of the sheet, the stamping pressure can be uniform or varying.

[0432] The stamping pressure can be varied according to the area or film thickness of the pressed part. Furthermore, it is also possible to apply different pressures to the same part in stages.

[0433] The stamped surface can be smooth or rough.

[0434] <Initialization>

[0435] All-solid-state secondary batteries manufactured in the manner described above are preferably initialized after manufacturing or before use. There are no particular limitations on initialization; for example, initial charging and discharging can be performed under increased stamping pressure, followed by releasing the pressure until the normal operating pressure of the all-solid-state secondary battery is reached.

[0436] Applications of all-solid-state rechargeable batteries

[0437] The all-solid-state secondary battery of this invention is applicable to a wide variety of uses. There are no particular limitations on its application; for example, when incorporated into electronic devices, it can be used in laptops, pen-and-paper computers, mobile computers, e-book readers, mobile phones, cordless phones, pagers, handheld terminals, portable fax machines, portable copiers, portable printers, stereo headphones, camcorders, LCD TVs, handheld vacuum cleaners, portable CD players, mini disk drives, electric shavers, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, etc. As other civilian products, it can be used in automobiles, electric vehicles, motors, lighting fixtures, toys, game consoles, load conditioners, clocks, flashlights, cameras, and medical devices (pacemakers, hearing aids, and shoulder massagers, etc.). Furthermore, it can be used in various military and aerospace applications. It can also be combined with solar cells.

[0438] Example

[0439] The present invention will now be described in further detail with reference to embodiments, but the invention is not limited thereto. In the following embodiments, unless otherwise specified, "parts" and "%" of composition refer to mass. In the present invention, "room temperature" refers to 25°C.

[0440] 1. Preparation of compounds containing metallic elements

[0441] The metal-containing compounds used to prepare compositions containing inorganic solid electrolytes are commercially available products, and the compounds represented by symbols in Table 1 are the same as those appended to the illustrative compounds above.

[0442] For each metal-containing compound, Table 1 shows its solubility and dispersion state, valence (number of metal elements in the molecule), pKa of the conjugate acid of the anion (based on the above determination method), and the number of carbon atoms of the organic compound forming the anion in the inorganic solid electrolyte composition described later. Furthermore, Table 1 shows the results obtained by determining the average particle size of the metal-containing compounds after preparing the inorganic solid electrolyte composition using the method described later.

[0443] The solubility and dispersion state of metal-containing compounds in inorganic solid electrolyte compositions are classified as follows.

[0444] -Solubility-

[0445] Dissolution: Indicates that it exists in a dissolved state, and the solubility relative to butyl butyrate, as determined by the above method, is 80% by mass or more.

[0446] Solid: indicates that it exists in a solid state, and the solubility mentioned above is less than 0.05% by mass.

[0447] -Dispersion-

[0448] Similar to the preparation of each composition, the dispersibility of the metal-containing compound was classified based on the amount of solid content reduction determined in the same manner as in Evaluation 1: Dispersion Stability Test described later.

[0449] Dispersion: Indicates the dispersed state, with a reduction in solid content of less than 5% by mass.

[0450] Non-dispersed: Indicates a non-dispersed state, with a reduction in solid content of 5% or more by mass.

[0451] [Table 1]

[0452]

[0453] <Abbreviation for table>

[0454] C-11: The above-mentioned exemplary compound C-11

[0455] C-12: The above-mentioned exemplary compound C-12

[0456] C-14: The above-mentioned exemplary compound C-14

[0457] C-15: The above-mentioned exemplary compound C-15

[0458] C-16: The following compounds have C-16

[0459] LiTFSI: Lithium bis(trifluoromethanesulfonyl)imide (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0460] [Chemical Formula 3]

[0461]

[0462] 2. Polymer synthesis and preparation of adhesive solutions or dispersions

[0463] The following polymers B-1 to B-9, with the chemical formulas listed below and shown in Table 2, were synthesized.

[0464] [Synthesis Example 1: Synthesis of Polymer B-1 and Preparation of Adhesive Solution B-1]

[0465] A monomer solution was prepared by adding 70 g of styrene (manufactured by FUJIFILM Wako Pure Chemical Corporation), 29.7 g of dodecyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.3 g of maleic anhydride (manufactured by FUJIFILM Wako Pure Chemical Corporation), and 0.36 g of polymerization initiator V-601 (trade name, manufactured by FUJIFILM Wako Pure Chemical Corporation) to a 100 mL flask and dissolving them in 36 g of butyl butyrate. 18 g of butyl butyrate was added to a 300 mL three-necked flask, and the monomer solution was added dropwise over 2 hours with stirring at 80 °C. After the addition was complete, the temperature was raised to 90 °C and stirred for 2 hours. The resulting solution was precipitated again in methanol, and the solid obtained was dried at 80 °C and dissolved in butyl butyrate to obtain the target polymer.

[0466] Thus, polymer B-1 (ethylene-based polymer, mass-average molecular weight 77,000) was synthesized, and a solution B-1 (concentration 10% by mass) of adhesive composed of polymer B-1 was obtained.

[0467] [Synthesis Example 2: Preparation of Adhesive Dispersion B-2]

[0468] Methyl methacrylate (trade code: M0088, mass average molecular weight 90,000, manufactured by Tokyo Chemical Industry Co., Ltd.) was dispersed in butyl butyrate to obtain a dispersion B-2 (concentration 10% by mass) of an adhesive composed of (meth)acrylic acid polymer B-2.

[0469] [Synthesis Example 3: Synthesis of Polymer B-3 and Preparation of Adhesive Solution B-3]

[0470] 28.80 g of NISSO-PB GI1000 (trade name, manufactured by Nippon Soda Co., Ltd.), 1.92 g of polypropylene glycol (PPG400, manufactured by FUJIFILM Wako Pure Chemical Corporation), and 0.11 g of 2,2-bis(hydroxymethyl)butyric acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added to a 200 mL three-necked flask and dissolved in 55.5 g of butyl butyrate (manufactured by Tokyo Chemical Industry Co., Ltd.). 6.30 g of dicyclohexylmethane-4,4'-diisocyanate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to this solution and stirred at 80 °C until homogeneous. 100 mg of NEOSTANNU-600 (trade name, manufactured by Nitto Kasei Co., Ltd.) was added to the resulting solution, and the mixture was stirred at 80 °C for 10 hours.

[0471] Thus, polymer B-3 (polyurethane, mass-average molecular weight 32,000) was synthesized, and a solution B-3 (concentration 10% by mass) of adhesive composed of polymer B-3 was obtained.

[0472] [Synthesis Example 4: Synthesis of Polymer B-4 and Preparation of Adhesive Solution B-4]

[0473] In Synthesis Example 1, except that maleic anhydride was replaced with 0.3 g of vinyl acetate and 1.0 g of phosphoric acid, polymer B-4 (ethylene polymer, mass average molecular weight 60,000) was synthesized in the same manner as in Synthesis Example 1, and a solution B-4 (concentration 10% by mass) of the adhesive composed of polymer B-4 was obtained.

[0474] [Synthesis Example 5: Synthesis of Polymer B-5 and Preparation of Adhesive Solution B-5]

[0475] 150 parts by mass of toluene, 30 parts by mass of styrene, and 70 parts by mass of 1,3-butadiene were added to an autoclave, along with 1 part by mass of polymerization initiator V-601 (manufactured by Wako Pure Chemical Industries, Ltd.). The mixture was heated to 80°C and stirred for 3 hours. Then, the temperature was increased to 90°C, and the reaction was continued until the conversion rate reached 100%. The resulting solution was precipitated again in methanol, and the solid was dried. 100 parts by mass of the resulting polymer were then added to 3 parts by mass of 2,6-di-tert-butyl-p-cresol and 0.3 parts by mass of maleic anhydride, and reacted at 180°C for 5 hours. The resulting solution was precipitated again in methanol, and the solid was dried at 80°C to obtain the target polymer (dry solid). The mass-average molecular weight of this polymer was 89,000. Then, after dissolving 50 parts by mass of the obtained polymer (dry solids) in 50 parts by mass of cyclohexane and 150 parts by mass of THF (tetrahydrofuran), the solution was set to 70°C, and 3 parts by mass of n-butyllithium, 3 parts by mass of 2,6-di-tert-butyl-p-cresol, 1 part by mass of bis(cyclopentadienyl)titanium dichloride, and 2 parts by mass of diethylaluminum chloride were added, under a hydrogen pressure of 10 kg / cm². 2 The reaction was carried out for 1 hour, then distilled off and dried to synthesize polymer B-5 (hydrocarbon polymer, mass average molecular weight 89,000). By dissolving it in butyl butyrate, a solution B-5 (concentration 10% by mass) of the adhesive composed of polymer B-5 was obtained.

[0476] [Synthesis Example 6: Synthesis of Polymer B-6 and Preparation of Adhesive Solution B-6]

[0477] 150 parts by mass of toluene, 30 parts by mass of styrene, and 70 parts by mass of 1,3-butadiene were added to an autoclave, along with 1 part by mass of polymerization initiator V-601 (manufactured by Wako Pure Chemical Industries, Ltd.). The mixture was heated to 80°C and stirred for 3 hours. Then, the temperature was increased to 90°C, and the reaction was continued until the conversion rate reached 100%. The resulting solution was precipitated again in methanol, and the solid was dried to obtain 100 parts by mass of the polymer. 3 parts by mass of 2,6-di-tert-butyl-p-cresol and 0.5 parts by mass of maleic anhydride were added, and the reaction was carried out at 180°C for 5 hours. The resulting solution was precipitated again in acetonitrile, and the solid was dried at 80°C to obtain the polymer (dry solid). The mass-average molecular weight of this polymer was 90,000. Then, after dissolving 50 parts by mass of the obtained polymer (dry solids) in 50 parts by mass of cyclohexane and 150 parts by mass of THF (tetrahydrofuran), the solution was set to 70°C, and 3 parts by mass of n-butyllithium, 3 parts by mass of 2,6-di-tert-butyl-p-cresol, 1 part by mass of bis(cyclopentadienyl)titanium dichloride, and 2 parts by mass of diethylaluminum chloride were added, under a hydrogen pressure of 10 kg / cm². 2 The reaction was carried out for 1 hour, then removed by distillation and dried to obtain hydrocarbon polymer precursor A (mass average molecular weight 90,000).

[0478] Next, 450 parts by mass of xylene (manufactured by FUJIFILM Wako Pure Chemical Corporation) and 50 parts by mass of the aforementioned hydrocarbon polymer precursor A were added to a 1L three-necked flask equipped with a reflux condenser and a gas inlet plug and dissolved. Then, 2 parts by mass of 1H,1H,2H,2H-perfluoro-1-octanol (manufactured by FUJIFILM Wako Pure Chemical Corporation) were added, the temperature was raised to 130°C, and stirring was continued for 20 hours. Then, it was added dropwise to methanol, and polymer B-6 was obtained as a precipitate. After drying under reduced pressure at 60°C for 5 hours, it was dissolved in any solvent. Thus, polymer B-6 (mass average molecular weight 99,000) was synthesized, and a solution B-6 (concentration 10% by mass) of the binder composed of polymer B-6 (hydrocarbon polymer) was obtained.

[0479] [Synthesis Example 7: Synthesis of Polymer B-7 and Preparation of Adhesive Solution B-7]

[0480] 450 parts by mass of xylene (manufactured by FUJIFILM Wako Pure Chemical Corporation) and 50 parts by mass of the aforementioned hydrocarbon polymer precursor A were placed in a 1L three-necked flask equipped with a reflux condenser and a gas inlet plug and dissolved. Then, 10 parts by mass of 1H,1H,2H,2H-perfluoro-1-dodecanethiol (manufactured by Sigma-Aldrich Co. LLC.) and 2 parts by mass of azobisisobutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation) were added, and nitrogen gas was introduced at a flow rate of 200 mL / min for 10 minutes. The temperature was then raised to 80°C and stirred for 5 hours. The mixture was then added dropwise to methanol, and polymer B-7 was obtained as a precipitate. The polymer was dried under reduced pressure at 60°C for 5 hours and then dissolved in any solvent.

[0481] Thus, polymer B-7 (mass average molecular weight 99,000) was synthesized, and a solution B-7 (concentration 10% by mass) of an adhesive composed of polymer B-7 (hydrocarbon polymer) was obtained.

[0482] [Synthesis Example 8: Synthesis of Polymer B-8 and Preparation of Adhesive Solution B-8]

[0483] The 1H,1H,2H,2H-perfluoro-1-octanol in Synthesis Example 6 was replaced with a modified silicone oil with hydroxyl groups at the end of the film (trade name: X-22-170BX, manufactured by Shin-Etsu Chemical Co., Ltd.). Otherwise, polymer B-8 (mass average molecular weight 101,000) was synthesized in the same manner as in Synthesis Example 6, and a solution B-8 (concentration 10% by mass) of an adhesive composed of polymer B-8 (hydrocarbon polymer) was obtained.

[0484] [Synthesis Example 9: Synthesis of Polymer B-9 and Preparation of Adhesive Solution B-9]

[0485] 500 parts by weight of xylene (manufactured by FUJIFILM WakoPure Chemical Corporation), 10 parts by weight of 6-mercapto-1-hexanol (manufactured by Tokyo Chemical Industry Co., Ltd.), 330 parts by weight of lauryl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 180 parts by weight of 1H,1H,2H,2H-tridecylfluoro-n-octyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), and 20 parts by weight of azobisisobutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation) were added to a 1L three-necked flask equipped with a reflux condenser and a gas inlet plug. Nitrogen gas was introduced at a flow rate of 200 mL / min for 10 minutes, followed by heating to 80°C and stirring for 5 hours. Then, the mixture was added dropwise to methanol, and the B-9 precursor (macromonomer) was obtained as a precipitate. The number average molecular weight of the macromonomer was 4,200.

[0486] Next, the 1H,1H,2H,2H-perfluoro-1-octanol of Synthesis Example 6 was replaced with the aforementioned B-9 precursor. Otherwise, polymer B-9 (mass average molecular weight 102,000) was synthesized in the same manner as in Synthesis Example 6, and a solution B-9 (concentration 10% by mass) of the binder composed of polymer B-9 (hydrocarbon polymer) was obtained.

[0487] Polymers B-1 to B-9 are shown below. The numbers listed below each component indicate the content (mol%) of each component in the polymer. In the following formulas, Me represents methyl, R S1 R represents an alkylene group having 1 to 10 carbon atoms. S2 Indicates an alkyl group having 1 to 10 carbon atoms.

[0488] [Chemical Formula 4]

[0489]

[0490] Polymers B-10 to B-13, with the following chemical formulas and shown in Table 2, were synthesized as follows. [Synthesis Example 10: Synthesis of Polymer B-10 and Preparation of Adhesive Solution B-10]

[0491] 150 parts by mass of toluene, 30 parts by mass of styrene, and 70 parts by mass of 1,3-butadiene were added to an autoclave, along with 1 part by mass of polymerization initiator V-601 (manufactured by Wako Pure Chemical Industries, Ltd.). The mixture was heated to 80°C and stirred for 3 hours. Then, the temperature was increased to 90°C, and the reaction was continued until the conversion rate reached 100%. The resulting solution was precipitated again in methanol, and the solid was dried to obtain 100 parts by mass of the polymer. 3 parts by mass of 2,6-di-tert-butyl-p-cresol and 0.5 parts by mass of maleic anhydride were added, and the reaction was carried out at 180°C for 5 hours. The resulting solution was precipitated again in acetonitrile, and the solid was dried at 80°C to obtain the polymer (dry solid). The mass-average molecular weight of this polymer was 90,000. Then, after dissolving 50 parts by mass of the obtained polymer (dry solids) in 50 parts by mass of cyclohexane and 150 parts by mass of THF (tetrahydrofuran), the solution was set to 70°C, and 3 parts by mass of n-butyllithium, 3 parts by mass of 2,6-di-tert-butyl-p-cresol, 1 part by mass of bis(cyclopentadienyl)titanium dichloride, and 2 parts by mass of diethylaluminum chloride were added, under a hydrogen pressure of 10 kg / cm². 2 The reaction was carried out for 1 hour, then removed by distillation and dried to obtain hydrocarbon polymer precursor A (mass average molecular weight 90,000).

[0492] Next, 450 parts by mass of xylene (manufactured by FUJIFILM Wako Pure Chemical Corporation) and 50 parts by mass of the aforementioned hydrocarbon polymer precursor A were added to a 1L three-necked flask equipped with a reflux condenser and a gas inlet plug and dissolved. Then, 4 parts by mass of N-methylethanolamine (manufactured by Tokyo Chemical Industry Co., Ltd.) were added, the temperature was raised to 90°C, and stirring was continued for 20 hours. Then, 1N hydrochloric acid aqueous solution was added, and the organic layer was separated and added dropwise to methanol to obtain polymer B-10 as a precipitate. After drying under reduced pressure at 60°C for 5 hours, it was dissolved in any solvent. Thus, polymer B-10 (mass average molecular weight 94,000) was synthesized, and solution B-10 (concentration 10% by mass) of the adhesive composed of polymer B-10 was obtained.

[0493] [Synthesis Example 11: Synthesis of Polymer B-11 and Preparation of Adhesive Solution B-11]

[0494] 450 parts by mass of xylene (manufactured by FUJIFILM WakoPure Chemical Corporation) and 50 parts by mass of hydrocarbon polymer precursor B (synthesized by changing 0.5 parts by mass of maleic anhydride to 2.2 parts by mass of maleic anhydride in the synthesis of the above-mentioned hydrocarbon polymer precursor A) were added to a 1L three-necked flask equipped with a reflux condenser and a gas inlet plug, and dissolved. Then, 5.6 parts by mass of diethanolamine (manufactured by Tokyo Chemical Industry Co., Ltd.) were added, the temperature was raised to 90°C, and stirring was continued for 20 hours. Then, 1N hydrochloric acid aqueous solution was added, and the organic layer was separated and added dropwise to methanol to obtain polymer B-11 as a precipitate. After drying under reduced pressure at 60°C for 5 hours, it was dissolved in any solvent. Thus, polymer B-11 (mass average molecular weight 95,000) was synthesized, and solution B-11 (concentration 10% by mass) of the binder composed of polymer B-11 was obtained.

[0495] [Synthesis Example 12: Synthesis of Polymer B-12 and Preparation of Adhesive Solution B-12]

[0496] 450 parts by mass of xylene (manufactured by FUJIFILM Wako Pure Chemical Corporation) and 50 parts by mass of the aforementioned hydrocarbon polymer precursor A were placed in a 1L three-necked flask equipped with a reflux condenser and a gas inlet plug and dissolved. Then, 2.3 parts by mass of α-thioglycerol (manufactured by Tokyo Chemical Industry Co., Ltd.) and 2 parts by mass of azobisisobutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation) were added, and nitrogen gas was introduced at a flow rate of 200 mL / min for 10 minutes. The temperature was then raised to 80°C and stirred for 5 hours. The mixture was then added dropwise to methanol, and polymer B-12 was obtained as a precipitate. The precipitate was dried under reduced pressure at 60°C for 5 hours and then dissolved in any solvent. Thus, polymer B-12 (mass average molecular weight 98,000) was synthesized, yielding a solution B-12 (concentration 10% by mass) of polymer B-12 as an adhesive.

[0497] [Synthesis Example 13: Synthesis of Polymer B-13 and Preparation of Adhesive Solution B-13]

[0498] 100 parts by weight of xylene (manufactured by FUJIFILM Wako Pure Chemical Corporation) were injected into a 2L three-necked flask equipped with a reflux condenser and a gas inlet plug. Nitrogen gas was introduced at a flow rate of 100 mL / min for 10 minutes, and the temperature was raised to 80°C. A mixture of 9.2 parts by weight of 2-aminoethanethiol hydrochloride (manufactured by Tokyo Chemical Industry Co., Ltd.) and 100 parts by weight of ethanol (manufactured by FUJIFILM Wako Pure Chemical Corporation), and a mixture of 400 parts by weight of lauryl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 100 parts by weight of hydroxyethyl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 170 parts by weight of xylene (manufactured by FUJIFILM Wako Pure Chemical Corporation), and 10 parts by weight of azobisisobutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation) were added dropwise to the same three-necked flask over 2 hours. After addition, the mixture was stirred further at 80°C for 2 hours. Then, it was added dropwise to methanol, and as a precipitate, a macromonomer with terminal amino groups (hydrochloride) was obtained. The number average molecular weight of the macromonomer was 4,000.

[0499] Next, 450 parts by mass of xylene (manufactured by FUJIFILM Wako Pure Chemical Corporation) and 50 parts by mass of the aforementioned hydrocarbon polymer precursor B were added to a 1L three-necked flask equipped with a reflux cooling tube and a gas inlet plug and dissolved. Then, 68 parts by mass of the aforementioned terminal amino-terminated macromonomer and 1.6 parts by mass of 1,8-diazabicyclo(DBU, manufactured by FUJIFILM Wako Pure Chemical Corporation) were added, the temperature was raised to 130°C, and stirring was continued for 10 hours. Then, 1N hydrochloric acid aqueous solution was added, and the organic layer was separated and added dropwise to acetone to obtain polymer B-13 as a precipitate. After drying under reduced pressure at 60°C for 5 hours, it was dissolved in any solvent. Thus, polymer B-13 (mass average molecular weight 110,000) was synthesized, and solution B-13 (concentration 10% by mass) of the adhesive composed of polymer B-13 was obtained.

[0500] Polymers B-10 to B-13 are shown below. The numbers listed in the lower right corner of each component indicate the content (mol%) of each component in the polymer.

[0501] [Chemical Formula 5]

[0502]

[0503] The solubility of the polymer binders composed of the synthesized polymers relative to the dispersion medium (butyl butyrate) used to prepare the inorganic solid electrolyte composition described below was determined by the above method and is shown in Table 2. Furthermore, the solubility in the inorganic solid electrolyte composition described below was categorized based on the solubility measured. Table 2 also shows the presence (type) and content of functional groups of each synthesized polymer, as well as the pKa (the lowest value is shown when multiple functional groups are present) determined by the above method for determining functional groups.

[0504] The solubility of polymer adhesives is classified according to the following categories.

[0505] -Solubility-

[0506] Dissolved: Indicates existence in a dissolved state, with a measured solubility of 80% or more relative to butyl butyrate. Solid: Indicates existence in a solid state, with the above solubility being less than 30% by mass.

[0507] [Table 2]

[0508]

[0509] 3. Synthesis of sulfide-based inorganic solid electrolytes [Synthesis Example A]

[0510] The sulfide-based inorganic solid electrolyte was synthesized with reference to non-patent literature, T. Ohtomo, A. Hayashi, M. Tatsumisago, Y. Tsuchida, S. Hama, K. Kawamoto, Journal of Power Sources, 233, (2013), pp231-235 and A. Hayashi, S. Hama, H. Morimoto, M. Tatsumisago, T. Minami, Chem. Lett., (2001), pp872-873.

[0511] Specifically, 2.42 g of lithium sulfide (Li2S, manufactured by Aldrich, Inc., purity >99.98%) and 3.90 g of phosphorus pentasulfide (P2S5, manufactured by Aldrich, Inc., purity >99%) were weighed out in a glove box under argon atmosphere (dew point -70°C) and placed into an agate mortar. The mixture was then mixed for 5 minutes using an agate pestle. The molar ratio of Li2S to P2S5 was set as Li2S:P2S5 = 75:25.

[0512] Next, 66g of 5mm diameter zirconia beads were added to a 45mL zirconia container (manufactured by Fritsch Co., Ltd.), along with the total amount of the aforementioned mixture of lithium sulfide and phosphorus pentasulfide. The container was then completely sealed under argon atmosphere. The container was placed in a planetary ball mill P-7 (trade name, manufactured by Fritsch Co., Ltd.) and mechanically ground at 25°C and 510 rpm for 20 hours, yielding 6.20g of a yellow powder sulfide-based inorganic solid electrolyte (Li-PS glass, hereinafter, sometimes labeled LPS). The average particle size of the Li-PS glass was 15μm.

[0513] [Example 1]

[0514] <Preparation of Inorganic Solid Electrolyte Compositions>

[0515] 60 g of 5 mm diameter zirconia beads were added to a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.). LPS synthesized in Synthetic Example A, the binder solutions or dispersions shown in Tables 3-3 and 3-4, the metal-containing compound, and butyl butyrate as the dispersion medium were added in the mass ratios shown in Tables 3-3 and 3-4 (wherein the mass of the solution or dispersion is the solid component). The container was then placed in a Fritsch Co., Ltd. planetary ball mill P-7 (trade name). Mixing was performed at 25 °C and 150 rpm for 10 minutes to prepare inorganic solid electrolyte compositions (slurries) S-31 and S-32, respectively.

[0516] <Preparation of Positive Electrode Compositions>

[0517] 60 g of 5 mm diameter zirconia beads were added to a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.) in the mass ratios shown in the tables. The LPS synthesized in Synthesis Example A and the dispersion media shown in Tables 3-1 and 3-3 were added as the dispersion media. The container was placed in a Fritsch Co., Ltd. P-7 planetary ball mill (trade name) and stirred at 25°C and 200 rpm for 30 minutes. Then, NMC as the positive electrode active material, acetylene black (AB) as the conductive additive, the binder solution or dispersion shown in Tables 3-2 and 3-4, and the metal element compound were added to the container in the mass ratios shown in Tables 3-1 and 3-3 (wherein the solution or dispersion is the mass of the solid component). The container was placed in a planetary ball mill P-7 and mixed for 30 minutes at a temperature of 25°C and a speed of 200 rpm to prepare positive electrode compositions (slurries) S-1 to S-28 and S-33 to S-36, respectively.

[0518] <Preparation of the composition for negative electrode>

[0519] 60 g of 5 mm diameter zirconia beads were added to a 45 mL container (manufactured by Fritsch Co., Ltd.), and LPS synthesized in Synthesis Example A, the binder solution or dispersion shown in Table 3-4, and the dispersion medium shown in Table 3-3 were added in the mass ratios shown in Tables 3-3 and 3-4. The container was placed in a planetary ball mill P-7 (trade name) manufactured by Fritsch Co., Ltd., and mixed at 25°C and 300 rpm for 60 minutes. Then, silicon (Si) as the negative electrode active material, acetylene black (AB) as the conductive additive, and a metal element compound were added in the mass ratios shown in Tables 3-3 and 3-4 (wherein the solution or dispersion is the mass of the solid component). The container was similarly placed in a planetary ball mill P-7 and mixed at 25°C and 100 rpm for 10 minutes to prepare negative electrode compositions (slurries) S-29 and S-30, respectively.

[0520] The results of measuring the viscosity of each prepared composition using the above-described method are shown in Tables 3-1 to 3-4 (collectively referred to as Table 3.) as the difference between the pKa of the conjugate acid and the pKa of the functional group in the metal-containing compound.

[0521] <Determination of the average particle size of compounds containing metallic elements>

[0522] The average particle size of the metal-containing compounds present in solid state in each of the prepared compositions was determined by the following method, and the results are shown in Tables 1 and 3.

[0523] -Determination Method-

[0524] The prepared compositions were passed through a filter cloth (10 μm diameter) to remove aggregates such as inorganic solid electrolytes, followed by centrifugation (500 rpm for 30 minutes). The separated supernatant (a mixture containing metal element compounds) was diluted with a dispersion medium (the same type used to prepare each composition) in a laser diffraction / scattering particle size distribution measuring device (trade name: LA-920, manufactured by HORIBA, Ltd.) to adjust the absorbance to 80-95%, and the absorbance was measured. The measurement conditions were the same as those for the average particle size of the inorganic solid electrolytes described above.

[0525]

[0526]

[0527]

[0528]

[0529] <Abbreviation for table>

[0530] In the table, "-" in each column indicates that the corresponding component is not present, or that the corresponding characteristics are not present, or that the corresponding characteristics cannot be determined.

[0531] The content of the dispersion medium is expressed as a percentage (mass%) relative to the total amount of the composition, and the content of other components is expressed as a percentage (mass%) relative to the solid components of the composition.

[0532] When the polymer has multiple functional groups (a), "pKa(D)" and "pKa difference" in the table represent the lowest pKa value and the difference between the lowest pKa value and the lowest pKa value.

[0533] LPS: LPS synthesized in Synthesis Example A

[0534] BB: Butyl butyrate

[0535] LiTFSI: Lithium bis(trifluoromethanesulfonyl)imide (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0536] C-11: The above-mentioned exemplary compound C-11

[0537] C-12: The above-mentioned exemplary compound C-12

[0538] C-14: The above-mentioned exemplary compound C-14

[0539] C-15: The above-mentioned exemplary compound C-15

[0540] C-16: The above-mentioned compound C-16

[0541] B-1 to B-13: Polymer adhesives synthesized in the above synthetic examples 1 to 13

[0542] NMC: LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (manufactured by Aldrich, CO.LTD.)

[0543] Si: Silicon (manufactured by Aldrich)

[0544] AB: Acetylene Black (manufactured by Denka Company Limited)

[0545] <Evaluation 1: Dispersion Stability Test>

[0546] Each prepared composition was placed in a glass test tube with a diameter of 10 mm and a height of 4 cm until the height reached 3.5 cm, and allowed to stand at 25°C for 24 hours. The reduction rate of solid content in the top 20% (height) of the slurry before and after standing was calculated using the above formula. The ease of precipitation (precipitability) of the inorganic solid electrolyte and active substances was evaluated as the dispersion stability of the composition, based on which of the following evaluation criteria this reduction rate of solid content was included in. The concentration of solid content was calculated by placing the collected slurry on an aluminum cup and heating it at 120°C for 2 hours to distill away the dispersion medium.

[0547] In this experiment, the smaller the reduction rate of the above-mentioned solid components, the better the dispersion stability. An evaluation standard of "F" or above is considered acceptable. The results are shown in Table 4.

[0548] Solid content reduction rate (%) = [(Solid content concentration of the top 20% before settling - Solid content concentration of the top 20% after settling) / Solid content concentration of the top 20% before settling] × 100

[0549] -Evaluation Criteria-

[0550] A: Solid content reduction rate <1%

[0551] B: 1% ≤ reduction rate of solid content < 2%

[0552] C: 2% ≤ Solid content reduction rate < 3%

[0553] D: 3% ≤ Solid content reduction rate < 4%

[0554] E: 4% ≤ Solid content reduction rate < 5%

[0555] F: 5% ≤ Solid content reduction rate < 6%

[0556] G: 6% ≤ reduction rate of solid content

[0557] <Evaluation 2: Processability>

[0558] Using the same method as the prepared compositions, except for the dispersion medium, and with a reduced amount of dispersion medium, a slurry with a solids concentration of 75% by mass was prepared. A 2 mL polyspot (manufactured by Atect Corporation) was vertically positioned so that the tip 10 mm penetrated below the slurry interface, and the slurry was aspirated at 25°C for 10 seconds. The mass W of the polyspot containing the aspirated slurry was measured. When the tare weight (self-weight) of the polyspot was set as W0, a slurry mass W - W0 less than 0.1 g was considered unabsorbable by dropper. When the slurry could not be aspirated by dropper, the upper limit of solids concentration that could be aspirated by dropper while gradually adding dispersion medium was determined. The processability of the composition (whether it has an appropriate viscosity to form a flat and well-surfaced constituent layer) was evaluated based on which of the following evaluation criteria the obtained upper limit of solids concentration falls into. The solids concentration was calculated by placing 0.30 g of the prepared slurry on an aluminum cup and heating it at 120°C for 2 hours to distill off the dispersion medium.

[0559] In this experiment, the higher the concentration of the above-mentioned upper limit solid components, the better the treatability, and the evaluation standard "F" and above is the qualified level. The results are shown in Table 4.

[0560] -Evaluation Criteria-

[0561] A: 75% ≤ Upper limit of solid content concentration

[0562] B: 70% ≤ Upper limit of solid component concentration < 75%

[0563] C: 65% ≤ Upper limit of solid content concentration < 70%

[0564] D: 60% ≤ Upper limit of solid content concentration < 65%

[0565] E: 55% ≤ Upper limit of solid content concentration < 60%

[0566] F: 50% ≤ Upper limit of solid content concentration < 55%

[0567] G: Upper limit of solid content concentration < 50%

[0568] <Fabrication of Solid Electrolyte Sheets for All-Solid-State Secondary Batteries>

[0569] Using a baking applicator (trade name: SA-201, manufactured by TESTER SANGYO CO,.LTD.), the inorganic solid electrolyte compositions S-31 and S-32 obtained above were coated onto aluminum foil with a thickness of 20 μm. The coatings were then heated at 80°C for 2 hours and dried (to remove the dispersion medium and induce a salt exchange reaction). Subsequently, using a hot press, the dried inorganic solid electrolyte compositions were heated and pressurized at 120°C and 40 MPa for 10 seconds to produce solid electrolyte sheets S-31 and S-32 for all-solid-state secondary batteries. The thickness of the solid electrolyte layer was 50 μm.

[0570] <Fabrication of Positive Electrode Sheets for All-Solid-State Secondary Batteries>

[0571] Using a baking applicator (trade name: SA-201), the above-obtained positive electrode compositions S-1 to S-28 and S-33 to S-36 were coated onto aluminum foil with a thickness of 20 μm. The coatings were heated at 80°C for 1 hour, then further heated at 110°C for 1 hour, and dried (to remove the dispersion medium and induce a salt exchange reaction). Then, using a hot press, the dried positive electrode compositions were pressurized at 25°C (10 MPa, 1 minute) to produce positive electrode sheets S-1 to S-28 and S-33 to S-36 for all-solid-state secondary batteries, each having a 100 μm thick positive electrode active material layer.

[0572] <Fabrication of negative electrode sheets for all-solid-state secondary batteries>

[0573] Using a baking applicator (trade name: SA-201), the aforementioned negative electrode compositions S-29 and S-30 were coated onto aluminum foil with a thickness of 20 μm. The foil was heated at 80°C for 1 hour, then further heated at 110°C for 1 hour, and dried (to remove the dispersion medium and induce a salt exchange reaction). Then, using a hot press, the dried negative electrode compositions were pressurized at 25°C (10 MPa, 1 minute) to produce all-solid-state secondary battery negative electrode sheets S-29 and S-30, each with a negative electrode active material layer with a film thickness of 70 μm.

[0574] <Evaluation 3: Determination of the average particle size of the polymer binder in the solid electrolyte layer or active material layer>

[0575] The prepared solid electrolyte sheet, positive electrode sheet, and negative electrode sheet for all-solid-state secondary batteries were pressed at 350 MPa for 30 seconds, bent at 180°, and then cut. The cross-sections of the exposed solid electrolyte layer or active material layer due to the fracture were observed (SEM images) at 10,000x magnification using a scanning electron microscope (SEM, model: JSM-7401F, manufactured by JEOL).

[0576] In the SEM images, 10 regions originating from the polymer binder were extracted, and the circular equivalent diameter of each region was calculated. The average of these diameters was used as the average particle size of the polymer binder (the polymer binder cured during the film formation process) in each layer. The results are shown in the "Average Particle Size in Layers" column of Table 3. Regions originating from the polymer binder in the SEM images are identified by the difference in contrast with the solid electrolyte.

[0577] By measuring the average particle size of the polymer adhesives (SEM images), it was determined that the polymer adhesives dissolved in each composition were cured into particles, confirming that the polymer adhesives were locally adsorbed on the surface of the solid particles and that the surface was not completely covered.

[0578] In addition, for Nos. S-2 to S-4, S-20, S-30 and S-32, the average particle size in the layer could not be determined because the solvent polymer adhesive did not cure into particles (marked as "cannot be determined" in Table 3).

[0579] <Evaluation 4: Determination of the solubility of polymer binders extracted from solid electrolyte layers or active material layers>

[0580] Polymer binders were extracted from the prepared solid electrolyte sheet, positive electrode sheet, and negative electrode sheet for all-solid-state secondary batteries, respectively, as follows. The solubility of the obtained polymer binders relative to the dispersion medium used to prepare each composition was determined by the above method, and is shown in the "Solubility after extraction" column of Table 3.

[0581] When the solubility of the extracted polymer binder is less than that of the polymer binder used to prepare each composition, it is presumed that the polymer binder present in each layer receives metal ions from the metal-containing compound.

[0582] -Extraction Method-

[0583] The solid electrolyte layer or active material layer peeled from each sheet is impregnated in butyl butyrate and vibrated in an ultrasonic cleaner for 1 hour. Then it is centrifuged (500 rpm, 1 minute) to precipitate the inorganic solid electrolyte and active material, and the polymer adhesive is obtained from the supernatant.

[0584] <Manufacturing of All-Solid-State Secondary Batteries>

[0585] <Manufacturing of Batteries for Evaluation of Positive Electrode Sheets for All-Solid-State Secondary Batteries (No. S-1 to S-28 and S-33 to S-36)>

[0586] The positive electrode sheets S-1 to S-28 and S-33 to S-36 of each all-solid-state secondary battery were stamped into discs with a diameter of 10 mm and placed in a PET cylinder with an inner diameter of 10 mm. 30 mg of LPS synthesized in Synthesis Example A was placed on the positive electrode active material layer side inside the cylinder, and 10 mm diameter SUS rods were inserted from both ends of the cylinder. A pressure of 350 MPa was applied to the current collector side of the positive electrode sheet and the LPS through the SUS rods. After temporarily removing the SUS rods from the LPS side, 9 mm diameter disc-shaped In sheets (20 μm thick) and 9 mm diameter disc-shaped Li sheets (20 μm thick) were inserted onto the LPS inside the cylinder in this order. The removed SUS rods were then reinserted into the cylinder and fixed under a pressure of 50 MPa. Thus, evaluation all-solid-state secondary batteries (half-cells) S-1 to S-28 and S-33 to S-36 were obtained, which have a structure of aluminum foil (20 μm thick) - positive electrode active material layer (80 μm thick) - solid electrolyte layer (200 μm thick) - negative electrode active material (counter electrode) layer (In / Li sheet, 30 μm thick).

[0587] <Manufacturing of Evaluation Batteries for All-Solid-State Secondary Battery Negative Electrode Sheets (S-29 and S-30)>

[0588] The fabricated all-solid-state secondary battery negative electrode sheets S-29 and S-30 were stamped into 10mm diameter discs and placed inside a 10mm inner diameter polyethylene terephthalate (PET) cylinder. 30mg of LPS synthesized in Synthesis Example A was placed on the negative electrode active material layer side inside the cylinder, and 10mm diameter stainless steel (SUS) rods were inserted from both ends of the cylinder. A pressure of 350MPa was applied to the current collector side of the all-solid-state secondary battery negative electrode sheet and the LPS through the SUS rods. After temporarily removing the SUS rods from the LPS side, 9mm diameter disc-shaped indium (In) sheets (20μm thick) and 9mm diameter disc-shaped lithium (Li) sheets (20μm thick) were inserted onto the LPS inside the cylinder in this order. The removed SUS rods were then reinserted into the cylinder and fixed under a pressure of 50MPa. Thus, evaluation all-solid-state secondary batteries (half-cells) S-29 and S-30 were obtained, which have a structure of copper foil (20 μm thick) - negative electrode active material layer (60 μm thick) - solid electrolyte layer (200 μm thick) - positive electrode active material (counter electrode) layer (In / Li sheet, 30 μm thick).

[0589] (Manufacturing of batteries for evaluating solid electrolyte sheets (S-31 and S-32) for all-solid-state secondary batteries)

[0590] A positive electrode sheet (S-8) for all-solid-state secondary batteries is stamped into a disc shape with a diameter of 10 mm and placed inside a PET cylinder with an inner diameter of 10 mm. Solid electrolyte sheets S-31 and S-32 for all-solid-state secondary batteries are stamped into disc shapes with a diameter of 10 mm on the positive electrode active material layer side inside the cylinder and placed inside the cylinder. 10 mm SUS rods are inserted from both ends of the cylinder. A pressure of 350 MPa is applied to the current collector side of the positive electrode sheet and the aluminum foil side of the solid electrolyte sheet for all-solid-state secondary batteries through the SUS rods. The SUS rods are temporarily removed from the solid electrolyte sheet side of the solid electrolyte sheet for all-solid-state secondary batteries, and the aluminum foil is gently peeled off. Then, disc-shaped In sheets (20 μm thick) with a diameter of 9 mm and disc-shaped Li sheets (20 μm thick) with a diameter of 9 mm are sequentially inserted onto the solid electrolyte layer of the solid electrolyte sheet for all-solid-state secondary batteries inside the cylinder. The removed SUS rod was reinserted into the cylinder and fixed under a pressure of 50 MPa. This resulted in evaluation all-solid-state secondary batteries (half-cells) S-31 and S-32, which have a structure of aluminum foil (20 μm thick), a positive electrode active material layer (80 μm thick), a solid electrolyte layer (45 μm thick), and a negative electrode active material (counter electrode) layer (In / Li sheet, 30 μm thick).

[0591] <Evaluation 5: Cyclic Characteristics Test under High-Speed ​​Charge and Discharge Conditions>

[0592] For each of the manufactured all-solid-state secondary batteries used for evaluation, the discharge capacity retention was measured using the TOSCAT-3000 charge-discharge evaluation device (trade name, manufactured by TOYO SYSTEM Co., Ltd.).

[0593] Specifically, each evaluation-grade all-solid-state secondary battery was charged at 25°C to a current density of 0.1 mA / cm². 2 And continue discharging until the battery voltage reaches 3.6V. Then, discharge until the current density reaches 0.1mA / cm². 2 The battery voltage was maintained at 2.5V. One charge and one discharge cycle was considered one charge-discharge cycle, and this process was repeated for three cycles under the same conditions to initialize the battery. Then, a current density of 3.0 mA / cm² was applied. 2 Charge until the battery voltage reaches 3.6V, at a current density of 3.0mA / cm². 2A high-speed charge-discharge cycle, consisting of discharging until the battery voltage reaches 2.5V, was defined as one cycle. This high-speed charge-discharge cycle was repeated 1000 times. The discharge capacity of each all-solid-state secondary battery used for evaluation was measured at the first and 1000th high-speed charge-discharge cycles using a TOSCAT-3000 (trade name) charge-discharge evaluation device. The discharge capacity retention rate was calculated using the following formula, and this rate was applied to the following evaluation criteria to evaluate the cycle characteristics of the all-solid-state secondary batteries. In this test, an evaluation criterion of "F" or higher was considered acceptable. The results are shown in Table 4.

[0594] Discharge capacity retention (%) = (Discharge capacity in the 1000th cycle / Discharge capacity in the 1st cycle) × 100

[0595] In this experiment, the higher the evaluation standard, the better the battery performance (cycle characteristics), and the better the battery performance can be maintained even after repeated high-speed charge and discharge cycles (even after long-term use).

[0596] Furthermore, the discharge capacity of the all-solid-state secondary battery used for evaluation in this invention consistently showed values ​​sufficient for its function as an all-solid-state secondary battery. Moreover, even without the aforementioned high-speed charge-discharge cycle, but under the same initialization conditions as described above, the all-solid-state secondary battery used for evaluation in this invention maintained excellent cycle characteristics.

[0597] -Evaluation Criteria-

[0598] A: 90% ≤ Discharge Capacity Maintenance Rate

[0599] B: 85% ≤ Discharge Capacity Retention < 90%

[0600] C: 80% ≤ Discharge capacity retention < 85%

[0601] D: 75% ≤ Discharge Capacity Retention < 80%

[0602] E: 70% ≤ Discharge capacity retention < 75%

[0603] F: 60% ≤ Discharge capacity retention < 70%

[0604] G: Discharge capacity retention rate < 60%

[0605] <Evaluation 6: Measurement of Ion Conductivity>

[0606] The ionic conductivity of each of the manufactured all-solid-state secondary cells for evaluation was measured. Specifically, for each all-solid-state secondary cell for evaluation, the AC impedance was measured in a constant temperature bath at 25°C using a 1255B FREQUENCY RESPONSE ANALYZER (trade name, manufactured by SOLARTRON) up to a voltage amplitude of 5mV and a frequency of 1MHz to 1Hz. The resistance in the thickness direction of the sample used for ionic conductivity measurement was then determined, and the ionic conductivity was calculated using the following formula (1). This indicates that the higher the ionic conductivity, the lower the resistance of the all-solid-state secondary cell for evaluation.

[0607] Equation (1): Ionic conductivity σ (mS / cm) =

[0608] 1000 × sample layer thickness (cm) / [resistance (Ω) × sample area (cm²)] 2 )]

[0609] In equation (1), the sample layer thickness is the value obtained by subtracting the thickness of the current collector from the thickness of the all-solid-state secondary battery used for evaluation (the total layer thickness of the solid electrolyte layer and the electrode active material layer). The sample area is the area of ​​a circular plate-shaped sheet with a diameter of 10 mm.

[0610] Determine whether the obtained ionic conductivity σ is included in which of the following evaluation criteria? In this test, the ionic conductivity σ is considered acceptable if the evaluation benchmark is above "F". The results are shown in Table 4.

[0611] -Evaluation Criteria-

[0612] A: 1.5 ≤ σ (mS / cm)

[0613] B: 1.4 ≤ σ (mS / cm) < 1.5

[0614] C: 1.3≤σ(mS / cm <1.4

[0615] D: 1.2≤ σ ( m S / cm) < 1.3

[0616] E: 1.1 ≤ σ (mS / cm) < 1.2

[0617] F: 1.0 ≤ σ (mS / cm) < 1.1

[0618] G: σ(mS / cm) < 1.0

[0619] [Table 4]

[0620] S-1 positive electrode G G G G Comparative example S-2 positive electrode F E G E Comparative example S-3 positive electrode E G G G Comparative example S-4 positive electrode E G E G Comparative example S-5 positive electrode C C C C This invention S-6 positive electrode C C B B This invention S-7 positive electrode B B A B This invention S-8 positive electrode A A A A This invention S-9 positive electrode A B B B This invention S-10 positive electrode D C D D This invention S-11 positive electrode E D D D This invention S-12 positive electrode D C C C This invention S-13 positive electrode B A A A This invention S-14 positive electrode A A A A This invention S-15 positive electrode B B B C This invention S-16 positive electrode D D D C This invention S-17 positive electrode D C D C This invention S-18 positive electrode C C B C This invention S-19 positive electrode E D D D This invention S-20 positive electrode E G G G Comparative example S-21 positive electrode G G G G Comparative example S-22 positive electrode A A A B This invention S-23 positive electrode A A A A This invention S-24 positive electrode A A A A This invention S-25 positive electrode A A A A This invention S-26 positive electrode A A A A This invention S-27 positive electrode A A A A This invention S-28 positive electrode A A A A This invention S-33 positive electrode A A A A This invention S-34 positive electrode A A A A This invention S-35 positive electrode A A A A This invention S-36 positive electrode A A A A This invention S-29 negative electrode B A A A This invention S-30 negative electrode F G G E Comparative example S-31 solid electrolyte layer B A A A This invention S-32 solid electrolyte layer F G G E Comparative example

[0621] [Example 2]

[0622] In Example 2, using polymer binder B-1 composed of polymer B-1 synthesized in Synthesis Example 1 and lithium stearate as a metal element compound, the effects of temperature or concentration conditions and the solubility of polymer binder B-1, as well as the effect on resistance during the formation of the layer, were confirmed.

[0623] Specifically, butyl butyrate, polymer binder B-1, and lithium stearate were mixed as a dispersion medium to prepare a mixture in which the content of polymer binder B-1 was set at 10.0% by mass and the content of lithium stearate was set at 0.5% by mass. In the obtained mixture, polymer binder B-1 was dissolved and lithium stearate was dispersed (average particle size 0.80 μm). The solubility of polymer binder B-1 in the obtained mixture relative to butyl butyrate, determined by the above method, was 80% by mass.

[0624] The obtained mixtures were heated and concentrated at the concentrations and temperatures shown in the “Processing Conditions” column of Table 5 to obtain processed mixtures E-1 to E-9.

[0625] Table 5 shows the results of recovering the polymer binder from the treated mixtures E-1 to E-9 by the following methods, and determining the solubility of butyl butyrate as the dispersion medium used to prepare the mixture by the above methods.

[0626] -Methods for recovering polymeric adhesives from post-processed mixtures-

[0627] After treatment, the mixture was vacuum dried at room temperature for 20 hours in a vacuum test subject dryer (trade name: HD-15D, manufactured by ISHII LABORATORYWORKS CO.,LTD.) to recover the polymer adhesive.

[0628] Next, inorganic solid electrolyte, butyl butyrate, positive electrode active material, and conductive additives were mixed in the treated mixtures E-1 to E-9 in the same manner as the positive electrode composition S-8 prepared in Example 1 (the total content of polymer binder and lithium stearate is 1.05% by mass, polymer binder:lithium stearate = 100:5). Positive electrode compositions E-1 to E-9 were prepared respectively.

[0629] Using positive electrode compositions E-1 to E-9, positive electrode sheets for all-solid-state secondary batteries were fabricated in the same manner as in Example 1. Subsequently, batteries for evaluating the positive electrode sheets for all-solid-state secondary batteries were manufactured.

[0630] For the all-solid-state secondary battery positive electrode evaluation cells E-1 to E-9, the ionic conductivity σ was measured in the same manner as in <Evaluation 6: Ionic Conductivity Measurement> of Example 1, and the resistance was evaluated. The results are shown in Table 5.

[0631] [Table 5]

[0632]

[0633] The results shown in Tables 1 to 5 reveal the following:

[0634] The inorganic solid electrolyte compositions containing inorganic elements, shown in Comparative Examples S-1, S-3, S-4, S-20, S-30, and S-32, which do not contain the metal-containing compound specified in this invention, all fail to achieve both dispersion stability and processability, and exhibit poor dispersion characteristics. It is evident that the all-solid-state secondary batteries used in the evaluation process exhibit poor performance in at least one aspect of cycle characteristics and ionic conductivity. Furthermore, the inorganic solid electrolyte composition containing inorganic elements, shown in Comparative Example S-2, which does not contain the metal-containing compound specified in this invention, exhibits poor ionic conductivity. Moreover, the inorganic solid electrolyte composition containing inorganic elements, shown in Comparative Example S-21, which contains a particulate binder insoluble in the dispersion medium but does not contain a polymer binder soluble in the dispersion medium, exhibits poor dispersion stability and processability even when containing the metal-containing compound specified in this invention. The all-solid-state secondary batteries used in the evaluation process using composition S-21 do not exhibit sufficient cycle characteristics and ionic conductivity.

[0635] In contrast, the inorganic solid electrolyte compositions containing polymer binders and metal element compounds in the dispersion state (solubility) specified in this invention, as shown in S-5 to S-19, S-22 to S-29, S-31, and S-33 to S-36 of this invention, all possess high levels of both dispersion stability and processability. It is evident that by using these inorganic solid electrolyte compositions to form the constituent layers of an all-solid-state secondary battery, the resulting all-solid-state secondary battery achieves not only excellent cycle characteristics but also high ionic conductivity.

[0636] The reason for this is that, as shown in Example 2 (Table 5), during the film-forming process of the inorganic solid electrolyte composition, when the coated composition is heated to a drying temperature of 80°C or higher, or concentrated to a concentration of 30% by mass or higher, the solubility of the polymer binder in the treated composition is lower than that of the polymer binder in its dissolved state before treatment. It is inferred that this decrease in solubility is caused by the polymer binder in its dissolved state accepting lithium metal ions from the metal-containing compound. Furthermore, it is known that the greater the decrease in solubility, the greater the ion conductivity and the lower the resistance of the battery used for evaluation. This is inferred to be because the polymer binder easily solidifies into particles.

[0637] Symbol Explanation

[0638] 1-Negative current collector, 2-Negative active material layer, 3-Solid electrolyte layer, 4-Positive active material layer, 5-Positive current collector, 6-Working part, 10-All-solid-state secondary battery.

Claims

1. A composition containing an inorganic solid electrolyte for use in an all-solid-state secondary battery, comprising: Inorganic solid electrolytes possessing conductivity of ions belonging to Group 1 or Group 2 of the periodic table. polymer adhesives Metallic compounds that do not display the ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table and Dispersion medium, in, The inorganic solid electrolyte includes at least one of sulfide-based inorganic solid electrolytes, oxide-based inorganic solid electrolytes, halide-based inorganic solid electrolytes, and hydride-based solid electrolytes. The polymer forming the polymeric adhesive comprises at least one polymer selected from polyurethane, polyurea, polyamide, polyimide, polyester, polyether, polycarbonate, fluoropolymer, hydrocarbon polymer, vinyl polymer, and (meth)acrylic acid polymer, and includes 0.1 to 10 mol% of a component having a functional group selected from group (A) below in all its constituent components. The metal-containing compound includes at least one selected from the following organic acid metal salts, the following alkoxides, and the following organometallic compounds. The dispersion medium includes at least one compound selected from ester compounds, ketone compounds, ether compounds, aromatic compounds, and aliphatic compounds, with a CLogP value of 1.5 to 6. The polymer binder is dissolved in the dispersion medium, and the metal-containing compound exists in a solid state. The organic acid metal salt is an organic acid metal salt containing anions derived from organic acids having 1 to 22 carbon atoms and cations derived from metal elements. The alkoxide is an alkoxide containing an anion derived from an alcohol having 3 to 22 carbon atoms and a cation derived from a metal element, and the hydrocarbon compound constituting the alcohol is a chain or cyclic saturated hydrocarbon, a chain or cyclic unsaturated hydrocarbon, or an aromatic hydrocarbon. The organometallic compound is an organometallic compound comprising an anion derived from a hydrocarbon having 3 to 22 carbon atoms and a cation derived from a metal element, wherein the hydrocarbon is a chain or cyclic saturated hydrocarbon or a chain or cyclic unsaturated hydrocarbon. The difference between the pKa of the conjugate acid of the anion of the derived metal-containing compound and the pKa of the functional group is equal to (pKa of the conjugate acid) - (pKa of the functional group) and is greater than 2. <Functional Groups (A)> Hydroxyl, amino, carboxyl, sulfonyl, phosphate, phosphonic acid, thioalkyl, heterocyclic, carboxylic anhydride.

2. The inorganic solid electrolyte composition according to claim 1, wherein, The metal-containing compound is dispersed in the dispersion medium.

3. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The average particle size of the metal-containing compound is 0.1–5 μm.

4. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The metal-containing compound includes at least one selected from the organic acid metal salt or the alkoxide.

5. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The negative common logarithm [pKa] of the acid dissociation constant of the conjugate acid of the anion is -2 to 20.

6. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The organic acid, the alcohol, and the hydrocarbon each have 6 to 21 carbon atoms.

7. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The metallic elements include those belonging to Group 1 or Group 2 of the periodic table.

8. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The metallic element includes lithium.

9. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The polymer forming the polymeric adhesive comprises at least one polymer selected from polyurethanes, vinyl polymers, (meth)acrylic polymers, and hydrocarbon polymers, and contains 0.1 to 10 mol% of a component having a functional group selected from the functional group (A) in all its components.

10. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The organic acid includes at least one of organic carboxylic acids, organic sulfonic acids, organic phosphonic acids, and organic boric acids.

11. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, When the inorganic solid electrolyte composition is heated to above 80°C, the solubility of the polymer binder in the dispersion medium after heating becomes less than the solubility of the polymer binder in the dispersion medium before heating.

12. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, When the inorganic solid electrolyte composition is concentrated to a total concentration of 30% by mass or more of the polymer binder and the metal element compound in the inorganic solid electrolyte composition, the solubility of the concentrated polymer binder in the dispersion medium becomes less than the solubility of the polymer binder in the dispersion medium before concentration.

13. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, When the inorganic solid electrolyte composition is film-formed to form a layer, the solubility of the polymer binder present in the layer in the dispersion medium previously contained in the inorganic solid electrolyte composition becomes less than the solubility of the polymer binder previously contained in the inorganic solid electrolyte composition in the dispersion medium.

14. The inorganic solid electrolyte composition according to claim 1 or 2, wherein it contains an active substance.

15. The inorganic solid electrolyte composition according to claim 1 or 2, wherein it contains a conductive additive.

16. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The inorganic solid electrolyte is a sulfide-based inorganic solid electrolyte.

17. The inorganic solid electrolyte composition according to claim 1 or 2, wherein, The viscosity at a temperature of 23℃ and a shear rate of 10 / s is 300–4000 cP.

18. A sheet for an all-solid-state secondary battery, having a layer formed from the inorganic solid electrolyte composition according to any one of claims 1 to 17.

19. The sheet for all-solid-state secondary batteries according to claim 18, wherein, The polymer adhesive exists in the layer as particles with an average particle size of 10 to 800 nm.

20. The sheet for all-solid-state secondary batteries according to claim 18 or 19, wherein, The solubility of the polymer binder present in the layer in the dispersion medium previously contained in the inorganic solid electrolyte composition becomes less than the solubility of the polymer binder previously contained in the inorganic solid electrolyte composition in that dispersion medium.

21. An all-solid-state secondary battery, comprising sequentially a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein, At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is composed of the sheet material for all-solid-state secondary batteries as described in any one of claims 18 to 20.

22. A method for manufacturing a sheet for an all-solid-state secondary battery, wherein the inorganic solid electrolyte composition according to any one of claims 1 to 17 is used to form a film.

23. The method for manufacturing the sheet for all-solid-state secondary batteries according to claim 22, wherein, While the polymer binder contained in the inorganic solid electrolyte composition is cured into particles, a film is formed.

24. The method for manufacturing a sheet for an all-solid-state secondary battery according to claim 22 or 23, wherein, While reducing the solubility of the polymer binder contained in the inorganic solid electrolyte composition in the dispersion medium, the inorganic solid electrolyte composition is used to form a film.

25. The method for manufacturing a sheet for an all-solid-state secondary battery according to claim 22 or 23, wherein, The inorganic solid electrolyte composition is heated to above 80°C to form a film.

26. A method for manufacturing an all-solid-state secondary battery, wherein the all-solid-state secondary battery is manufactured by the manufacturing method according to any one of claims 22 to 25.

Citation Information

Patent Citations

  • Latex agglutination reaction measuring instrument

    JP1987022066A

  • Carbon sliding material

    JP1987095332A

  • Catalyst carrier and production thereof

    JP1990006856A

  • Four-wheel steering device

    JP1991045473A

  • Distortion compensator

    JP1993090844A